Replay of behavioral sequences in the medial prefrontal cortex during rule switching - Käfer, Karola; Nardin, Michele; Blahna, Karel; Csicsvari, Jozsef L (Neuron)
Temporally organized reactivation of experiences during awake immobility periods is thought to underlie cognitive processes like planning and evaluation. While replay of trajectories is well established for the hippocampus, it is unclear whether the medial prefrontal cortex (mPFC) can reactivate sequential behavioral experiences in the awake state to support task execution. We simultaneously recorded from hippocampal and mPFC principal neurons in rats performing a mPFC-dependent rule-switching task on a plus maze. We found that mPFC neuronal activity encoded relative positions between the start and goal. During awake immobility periods, the mPFC replayed temporally organized sequences of these generalized positions, resembling entire spatial trajectories. The occurrence of mPFC trajectory replay positively correlated with rule-switching performance. However, hippocampal and mPFC trajectory replay occurred independently, indicating different functions. These results demonstrate that the mPFC can replay ordered activity patterns representing generalized locations and suggest that mPFC replay might have a role in flexible behavior.

Nondivergence form quasilinear heat equations driven by space-time white noise - Gerencser, Mate (Annales de l'Institut Henri Poincaré C, Analyse non linéaire)
We give a Wong-Zakai type characterisation of the solutions of quasilinear heat equations driven by space-time white noise in 1 + 1 dimensions. In order to show that the renormalisation counterterms are local in the solution, a careful arrangement of a few hundred terms is required. The main tool in this computation is a general ‘integration by parts’ formula that provides a number of linear identities for the renormalisation constants.

Nuclear translocation of glutaminase GLS2 in human cancer cells associates with proliferation arrest and differentiation - López De La Oliva, Amada R.; Campos-Sandoval, José A.; Gómez-García, María C.; Cardona, Carolina; Martín-Rufián, Mercedes; Sialana, Fernando J.; Castilla, Laura; Bae, Narkhyun; Lobo, Carolina; Peñalver, Ana; García-Frutos, Marina; Carro, David; et al. (Scientific reports)
Glutaminase (GA) catalyzes the first step in mitochondrial glutaminolysis playing a key role in cancer metabolic reprogramming. Humans express two types of GA isoforms: GLS and GLS2. GLS isozymes have been consistently related to cell proliferation, but the role of GLS2 in cancer remains poorly understood. GLS2 is repressed in many tumor cells and a better understanding of its function in tumorigenesis may further the development of new therapeutic approaches. We analyzed GLS2 expression in HCC, GBM and neuroblastoma cells, as well as in monkey COS-7 cells. We studied GLS2 expression after induction of differentiation with phorbol ester (PMA) and transduction with the full-length cDNA of GLS2. In parallel, we investigated cell cycle progression and levels of p53, p21 and c-Myc proteins. Using the baculovirus system, human GLS2 protein was overexpressed, purified and analyzed for posttranslational modifications employing a proteomics LC-MS/MS platform. We have demonstrated a dual targeting of GLS2 in human cancer cells. Immunocytochemistry and subcellular fractionation gave consistent results demonstrating nuclear and mitochondrial locations, with the latter being predominant. Nuclear targeting was confirmed in cancer cells overexpressing c-Myc- and GFP-tagged GLS2 proteins. We assessed the subnuclear location finding a widespread distribution of GLS2 in the nucleoplasm without clear overlapping with specific nuclear substructures. GLS2 expression and nuclear accrual notably increased by treatment of SH-SY5Y cells with PMA and it correlated with cell cycle arrest at G2/M, upregulation of tumor suppressor p53 and p21 protein. A similar response was obtained by overexpression of GLS2 in T98G glioma cells, including downregulation of oncogene c-Myc. Furthermore, human GLS2 was identified as being hypusinated by MS analysis, a posttranslational modification which may be relevant for its nuclear targeting and/or function. Our studies provide evidence for a tumor suppressor role of GLS2 in certain types of cancer. The data imply that GLS2 can be regarded as a highly mobile and multilocalizing protein translocated to both mitochondria and nuclei. Upregulation of GLS2 in cancer cells induced an antiproliferative response with cell cycle arrest at the G2/M phase.

Evolutionarily unique mechanistic framework of clathrin-mediated endocytosis in plants - Narasimhan, Madhumitha; Johnson, Alexander J; Prizak, Roshan; Kaufmann, Walter; Tan, Shutang; Casillas Perez, Barbara E; Friml, Jiří (eLife)
In plants, clathrin mediated endocytosis (CME) represents the major route for cargo internalisation from the cell surface. It has been assumed to operate in an evolutionary conserved manner as in yeast and animals. Here we report characterisation of ultrastructure, dynamics and mechanisms of plant CME as allowed by our advancement in electron microscopy and quantitative live imaging techniques. Arabidopsis CME appears to follow the constant curvature model and the bona fide CME population generates vesicles of a predominantly hexagonal-basket type; larger and with faster kinetics than in other models. Contrary to the existing paradigm, actin is dispensable for CME events at the plasma membrane but plays a unique role in collecting endocytic vesicles, sorting of internalised cargos and directional endosome movement that itself actively promote CME events. Internalized vesicles display a strongly delayed and sequential uncoating. These unique features highlight the independent evolution of the plant CME mechanism during the autonomous rise of multicellularity in eukaryotes.

Evaluating Face2Gene as a tool to identify Cornelia de Lange syndrome by facial phenotypes - Latorre-Pellicer, Ana; Ascaso, Ángela; Trujillano, Laura; Gil-Salvador, Marta; Arnedo, Maria; Lucia-Campos, Cristina; Antoñanzas-Pérez, Rebeca; Marcos-Alcalde, Iñigo; Parenti, Ilaria; Bueno-Lozano, Gloria; Musio, Antonio; Puisac, Beatriz; et al. (International Journal of Molecular Sciences)
Characteristic or classic phenotype of Cornelia de Lange syndrome (CdLS) is associated with a recognisable facial pattern. However, the heterogeneity in causal genes and the presence of overlapping syndromes have made it increasingly difficult to diagnose only by clinical features. DeepGestalt technology, and its app Face2Gene, is having a growing impact on the diagnosis and management of genetic diseases by analysing the features of affected individuals. Here, we performed a phenotypic study on a cohort of 49 individuals harbouring causative variants in known CdLS genes in order to evaluate Face2Gene utility and sensitivity in the clinical diagnosis of CdLS. Based on the profile images of patients, a diagnosis of CdLS was within the top five predicted syndromes for 97.9% of our cases and even listed as first prediction for 83.7%. The age of patients did not seem to affect the prediction accuracy, whereas our results indicate a correlation between the clinical score and affected genes. Furthermore, each gene presents a different pattern recognition that may be used to develop new neural networks with the goal of separating different genetic subtypes in CdLS. Overall, we conclude that computer-assisted image analysis based on deep learning could support the clinical diagnosis of CdLS.

Outside the box: Abstraction-based monitoring of neural networks - Henzinger, Thomas A; Lukina, Anna; Schilling, Christian (24th European Conference on Artificial Intelligence)
Neural networks have demonstrated unmatched performance in a range of classification tasks. Despite numerous efforts of the research community, novelty detection remains one of the significant limitations of neural networks. The ability to identify previously unseen inputs as novel is crucial for our understanding of the decisions made by neural networks. At runtime, inputs not falling into any of the categories learned during training cannot be classified correctly by the neural network. Existing approaches treat the neural network as a black box and try to detect novel inputs based on the confidence of the output predictions. However, neural networks are not trained to reduce their confidence for novel inputs, which limits the effectiveness of these approaches. We propose a framework to monitor a neural network by observing the hidden layers. We employ a common abstraction from program analysis - boxes - to identify novel behaviors in the monitored layers, i.e., inputs that cause behaviors outside the box. For each neuron, the boxes range over the values seen in training. The framework is efficient and flexible to achieve a desired trade-off between raising false warnings and detecting novel inputs. We illustrate the performance and the robustness to variability in the unknown classes on popular image-classification benchmarks.

Higher order corrections to the mean-field description of the dynamics of interacting bosons - Bossmann, Lea; Pavlović, Nataša; Pickl, Peter; Soffer, Avy (Journal of Statistical Physics)
In this paper, we introduce a novel method for deriving higher order corrections to the mean-field description of the dynamics of interacting bosons. More precisely, we consider the dynamics of N d-dimensional bosons for large N. The bosons initially form a Bose–Einstein condensate and interact with each other via a pair potential of the form (N−1)−1Ndβv(Nβ·)forβ∈[0,14d). We derive a sequence of N-body functions which approximate the true many-body dynamics in L2(RdN)-norm to arbitrary precision in powers of N−1. The approximating functions are constructed as Duhamel expansions of finite order in terms of the first quantised analogue of a Bogoliubov time evolution.

Benchmarking tomographic acquisition schemes for high-resolution structural biology - Turoňová, Beata; Hagen, Wim J.H.; Obr, Martin; Mosalaganti, Shyamal; Beugelink, J. Wouter; Zimmerli, Christian E.; Kräusslich, Hans Georg; Beck, Martin (Nature Communications)
Cryo electron tomography with subsequent subtomogram averaging is a powerful technique to structurally analyze macromolecular complexes in their native context. Although close to atomic resolution in principle can be obtained, it is not clear how individual experimental parameters contribute to the attainable resolution. Here, we have used immature HIV-1 lattice as a benchmarking sample to optimize the attainable resolution for subtomogram averaging. We systematically tested various experimental parameters such as the order of projections, different angular increments and the use of the Volta phase plate. We find that although any of the prominently used acquisition schemes is sufficient to obtain subnanometer resolution, dose-symmetric acquisition provides considerably better outcome. We discuss our findings in order to provide guidance for data acquisition. Our data is publicly available and might be used to further develop processing routines.

Colonization of endophyte Acremonium sp. D212 in Panax notoginseng and rice mediated by auxin and jasmonic acid - Han, L; Zhou, X; Zhao, Y; Zhu, S; Wu, L; He, Y; Ping, X; Lu, X; Huang, W; Qian, J; Zhang, L; Jiang, X; et al. (Journal of Integrative Plant Biology)
Endophytic fungi can be beneficial to plant growth. However, the molecular mechanisms underlying colonization of Acremonium spp. remain unclear. In this study, a novel endophytic Acremonium strain was isolated from the buds of Panax notoginseng and named Acremonium sp. D212. The Acremonium sp. D212 could colonize the roots of P. notoginseng, enhance the resistance of P. notoginseng to root rot disease, and promote root growth and saponin biosynthesis in P. notoginseng. Acremonium sp. D212 could secrete indole‐3‐acetic acid (IAA) and jasmonic acid (JA), and inoculation with the fungus increased the endogenous levels of IAA and JA in P. notoginseng. Colonization of the Acremonium sp. D212 in the roots of the rice line Nipponbare was dependent on the concentration of methyl jasmonate (MeJA) (2 to 15 μM) and 1‐naphthalenacetic acid (NAA) (10 to 20 μM). Moreover, the roots of the JA signalling‐defective coi1‐18 mutant were colonized by Acremonium sp. D212 to a lesser degree than those of the wild‐type Nipponbare and miR393b‐overexpressing lines, and the colonization was rescued by MeJA but not by NAA. It suggests that the cross‐talk between JA signalling and the auxin biosynthetic pathway plays a crucial role in the colonization of Acremonium sp. D212 in host plants.

Upper edge of chaos and the energetics of transition in pipe flow - Budanur, Nazmi B; Marensi, Elena; Willis, Ashley P.; Hof, Björn (Physical Review Fluids)
In the past two decades, our understanding of the transition to turbulence in shear flows with linearly stable laminar solutions has greatly improved. Regarding the susceptibility of the laminar flow, two concepts have been particularly useful: the edge states and the minimal seeds. In this nonlinear picture of the transition, the basin boundary of turbulence is set by the edge state's stable manifold and this manifold comes closest in energy to the laminar equilibrium at the minimal seed. We begin this paper by presenting numerical experiments in which three-dimensional perturbations are too energetic to trigger turbulence in pipe flow but they do lead to turbulence when their amplitude is reduced. We show that this seemingly counterintuitive observation is in fact consistent with the fully nonlinear description of the transition mediated by the edge state. In order to understand the physical mechanisms behind this process, we measure the turbulent kinetic energy production and dissipation rates as a function of the radial coordinate. Our main observation is that the transition to turbulence relies on the energy amplification away from the wall, as opposed to the turbulence itself, whose energy is predominantly produced near the wall. This observation is further supported by the similar analyses on the minimal seeds and the edge states. Furthermore, we show that the time evolution of production-over-dissipation curves provides a clear distinction between the different initial amplification stages of the transition to turbulence from the minimal seed.

Local laws for polynomials of Wigner matrices - Erdös, László; Krüger, Torben H; Nemish, Yuriy (Journal of Functional Analysis)
We consider general self-adjoint polynomials in several independent random matrices whose entries are centered and have the same variance. We show that under certain conditions the local law holds up to the optimal scale, i.e., the eigenvalue density on scales just above the eigenvalue spacing follows the global density of states which is determined by free probability theory. We prove that these conditions hold for general homogeneous polynomials of degree two and for symmetrized products of independent matrices with i.i.d. entries, thus establishing the optimal bulk local law for these classes of ensembles. In particular, we generalize a similar result of Anderson for anticommutator. For more general polynomials our conditions are effectively checkable numerically.

From Wigner-Yanase-Dyson conjecture to Carlen-Frank-Lieb conjecture - Zhang, Haonan (Advances in Mathematics)
In this paper we study the joint convexity/concavity of the trace functions Ψp,q,s(A,B)=Tr(Bq2K∗ApKBq2)s, p,q,s∈R, where A and B are positive definite matrices and K is any fixed invertible matrix. We will give full range of (p,q,s)∈R3 for Ψp,q,s to be jointly convex/concave for all K. As a consequence, we confirm a conjecture of Carlen, Frank and Lieb. In particular, we confirm a weaker conjecture of Audenaert and Datta and obtain the full range of (α,z) for α-z Rényi relative entropies to be monotone under completely positive trace preserving maps. We also give simpler proofs of many known results, including the concavity of Ψp,0,1/p for 0<p<1 which was first proved by Epstein using complex analysis. The key is to reduce the problem to the joint convexity/concavity of the trace functions Ψp,1−p,1(A,B)=TrK∗ApKB1−p, −1≤p≤1, using a variational method.

Natural variation in a dendritic scaffold protein remodels experience-dependent plasticity by altering neuropeptide expression - Beets, Isabel; Zhang, Gaotian; Fenk, Lorenz A.; Chen, Changchun; Nelson, Geoffrey M.; Félix, Marie-Anne; de Bono, Mario (Neuron)
The extent to which behavior is shaped by experience varies between individuals. Genetic differences contribute to this variation, but the neural mechanisms are not understood. Here, we dissect natural variation in the behavioral flexibility of two Caenorhabditis elegans wild strains. In one strain, a memory of exposure to 21% O2 suppresses CO2-evoked locomotory arousal; in the other, CO2 evokes arousal regardless of previous O2 experience. We map that variation to a polymorphic dendritic scaffold protein, ARCP-1, expressed in sensory neurons. ARCP-1 binds the Ca2+-dependent phosphodiesterase PDE-1 and co-localizes PDE-1 with molecular sensors for CO2 at dendritic ends. Reducing ARCP-1 or PDE-1 activity promotes CO2 escape by altering neuropeptide expression in the BAG CO2 sensors. Variation in ARCP-1 alters behavioral plasticity in multiple paradigms. Our findings are reminiscent of genetic accommodation, an evolutionary process by which phenotypic flexibility in response to environmental variation is reset by genetic change.

Inferring symbolic dynamics of chaotic flows from persistence - Yalniz, Gökhan; Budanur, Nazmi B (Chaos)
We introduce “state space persistence analysis” for deducing the symbolic dynamics of time series data obtained from high-dimensional chaotic attractors. To this end, we adapt a topological data analysis technique known as persistent homology for the characterization of state space projections of chaotic trajectories and periodic orbits. By comparing the shapes along a chaotic trajectory to those of the periodic orbits, state space persistence analysis quantifies the shape similarity of chaotic trajectory segments and periodic orbits. We demonstrate the method by applying it to the three-dimensional Rössler system and a 30-dimensional discretization of the Kuramoto–Sivashinsky partial differential equation in (1+1) dimensions. One way of studying chaotic attractors systematically is through their symbolic dynamics, in which one partitions the state space into qualitatively different regions and assigns a symbol to each such region.1–3 This yields a “coarse-grained” state space of the system, which can then be reduced to a Markov chain encoding all possible transitions between the states of the system. While it is possible to obtain the symbolic dynamics of low-dimensional chaotic systems with standard tools such as Poincaré maps, when applied to high-dimensional systems such as turbulent flows, these tools alone are not sufficient to determine symbolic dynamics.4,5 In this paper, we develop “state space persistence analysis” and demonstrate that it can be utilized to infer the symbolic dynamics in very high-dimensional settings.

Weighted Poisson–Delaunay mosaics - Edelsbrunner, Herbert; Nikitenko, Anton (Theory of Probability and its Applications)
Slicing a Voronoi tessellation in ${R}^n$ with a $k$-plane gives a $k$-dimensional weighted Voronoi tessellation, also known as a power diagram or Laguerre tessellation. Mapping every simplex of the dual weighted Delaunay mosaic to the radius of the smallest empty circumscribed sphere whose center lies in the $k$-plane gives a generalized discrete Morse function. Assuming the Voronoi tessellation is generated by a Poisson point process in ${R}^n$, we study the expected number of simplices in the $k$-dimensional weighted Delaunay mosaic as well as the expected number of intervals of the Morse function, both as functions of a radius threshold. As a by-product, we obtain a new proof for the expected number of connected components (clumps) in a line section of a circular Boolean model in ${R}^n$.

In vitro shoot growth and adventitious rooting of Wikstroemia gemmata depends on light quality - Verstraeten, Inge; Buyle, H.; Werbrouck, S.; Van Labeke, M.C.; Geelen, D. (Israel Journal of Plant Sciences)
In vitro propagation of the ornamentally interesting species Wikstroemia gemmata is limited by the recalcitrance to form adventitious roots. In this article, two strategies to improve the rooting capacity of in vitro microcuttings are presented. Firstly, the effect of exogenous auxin was evaluated in both light and dark cultivated stem segments and also the sucrose-content of the medium was varied in order to determine better rooting conditions. Secondly, different spectral lights were evaluated and the effect on shoot growth and root induction demonstrated that the exact spectral composition of light is important for successful in vitro growth and development of Wikstroemia gemmata. We show that exogenous auxin cannot compensate for the poor rooting under unfavorable light conditions. Adapting the culture conditions is therefore paramount for successful industrial propagation of Wikstroemia gemmata.

Distribution of crosstalk values - Grah, Rok; Friedlander, Tamar

Supporting information - Grah, Rok; Friedlander, Tamar

Slow quantum thermalization and many-body revivals from mixed phase space - Michailidis, Alexios; Turner, C. J.; Papić, Z.; Abanin, D. A.; Serbyn, Maksym (Physical Review X)
The relaxation of few-body quantum systems can strongly depend on the initial state when the system’s semiclassical phase space is mixed; i.e., regions of chaotic motion coexist with regular islands. In recent years, there has been much effort to understand the process of thermalization in strongly interacting quantum systems that often lack an obvious semiclassical limit. The time-dependent variational principle (TDVP) allows one to systematically derive an effective classical (nonlinear) dynamical system by projecting unitary many-body dynamics onto a manifold of weakly entangled variational states. We demonstrate that such dynamical systems generally possess mixed phase space. When TDVP errors are small, the mixed phase space leaves a footprint on the exact dynamics of the quantum model. For example, when the system is initialized in a state belonging to a stable periodic orbit or the surrounding regular region, it exhibits persistent many-body quantum revivals. As a proof of principle, we identify new types of “quantum many-body scars,” i.e., initial states that lead to long-time oscillations in a model of interacting Rydberg atoms in one and two dimensions. Intriguingly, the initial states that give rise to most robust revivals are typically entangled states. On the other hand, even when TDVP errors are large, as in the thermalizing tilted-field Ising model, initializing the system in a regular region of phase space leads to a surprising slowdown of thermalization. Our work establishes TDVP as a method for identifying interacting quantum systems with anomalous dynamics in arbitrary dimensions. Moreover, the mixed phase space classical variational equations allow one to find slowly thermalizing initial conditions in interacting models. Our results shed light on a link between classical and quantum chaos, pointing toward possible extensions of the classical Kolmogorov-Arnold-Moser theorem to quantum systems.

Molecular evolution and diversification of proteins involved in miRNA maturation pathway - Moturu, Taraka Ramji; Sinha, Sansrity; Salava, Hymavathi; Thula, Sravankumar; Nodzyński, Tomasz; Vařeková, Radka Svobodová; Friml, Jiří; Simon, Sibu (Plants)
Small RNAs (smRNA, 19–25 nucleotides long), which are transcribed by RNA polymerase II, regulate the expression of genes involved in a multitude of processes in eukaryotes. miRNA biogenesis and the proteins involved in the biogenesis pathway differ across plant and animal lineages. The major proteins constituting the biogenesis pathway, namely, the Dicers (DCL/DCR) and Argonautes (AGOs), have been extensively studied. However, the accessory proteins (DAWDLE (DDL), SERRATE (SE), and TOUGH (TGH)) of the pathway that differs across the two lineages remain largely uncharacterized. We present the first detailed report on the molecular evolution and divergence of these proteins across eukaryotes. Although DDL is present in eukaryotes and prokaryotes, SE and TGH appear to be specific to eukaryotes. The addition/deletion of specific domains and/or domain-specific sequence divergence in the three proteins points to the observed functional divergence of these proteins across the two lineages, which correlates with the differences in miRNA length across the two lineages. Our data enhance the current understanding of the structure–function relationship of these proteins and reveals previous unexplored crucial residues in the three proteins that can be used as a basis for further functional characterization. The data presented here on the number of miRNAs in crown eukaryotic lineages are consistent with the notion of the expansion of the number of miRNA-coding genes in animal and plant lineages correlating with organismal complexity. Whether this difference in functionally correlates with the diversification (or presence/absence) of the three proteins studied here or the miRNA signaling in the plant and animal lineages is unclear. Based on our results of the three proteins studied here and previously available data concerning the evolution of miRNA genes in the plant and animal lineages, we believe that miRNAs probably evolved once in the ancestor to crown eukaryotes and have diversified independently in the eukaryotes.

LIS1 determines cleavage plane positioning by regulating actomyosin-mediated cell membrane contractility - Moon, Hyang Mi; Hippenmeyer, Simon; Luo, Liqun; Wynshaw-Boris, Anthony (eLife)
Heterozygous loss of human PAFAH1B1 (coding for LIS1) results in the disruption of neurogenesis and neuronal migration via dysregulation of microtubule (MT) stability and dynein motor function/localization that alters mitotic spindle orientation, chromosomal segregation, and nuclear migration. Recently, human induced pluripotent stem cell (iPSC) models revealed an important role for LIS1 in controlling the length of terminal cell divisions of outer radial glial (oRG) progenitors, suggesting cellular functions of LIS1 in regulating neural progenitor cell (NPC) daughter cell separation. Here we examined the late mitotic stages NPCs in vivo and mouse embryonic fibroblasts (MEFs) in vitro from Pafah1b1-deficient mutants. Pafah1b1-deficient neocortical NPCs and MEFs similarly exhibited cleavage plane displacement with mislocalization of furrow-associated markers, associated with actomyosin dysfunction and cell membrane hyper-contractility. Thus, it suggests LIS1 acts as a key molecular link connecting MTs/dynein and actomyosin, ensuring that cell membrane contractility is tightly controlled to execute proper daughter cell separation.

The lipid code-dependent phosphoswitch PDK1–D6PK activates PIN-mediated auxin efflux in Arabidopsis - Tan, Shutang; Zhang, Xixi; Kong, Wei; Yang, Xiao-Li; Molnar, Gergely; Vondráková, Zuzana; Filepová, Roberta; Petrášek, Jan; Friml, Jiří; Xue, Hong-Wei (Nature Plants)
Directional intercellular transport of the phytohormone auxin mediated by PIN FORMED (PIN) efflux carriers plays essential roles in both coordinating patterning processes and integrating multiple external cues by rapidly redirecting auxin fluxes. Multilevel regulations of PIN activity under internal and external cues are complicated; however, the underlying molecular mechanism remains elusive. Here we demonstrate that 3’-Phosphoinositide-Dependent Protein Kinase1 (PDK1), which is conserved in plants and mammals, functions as a molecular hub integrating the upstream lipid signalling and the downstream substrate activity through phosphorylation. Genetic analysis uncovers that loss-of-function Arabidopsis mutant pdk1.1 pdk1.2 exhibits a plethora of abnormalities in organogenesis and growth, due to the defective PIN-dependent auxin transport. Further cellular and biochemical analyses reveal that PDK1 phosphorylates D6 Protein Kinase to facilitate its activity towards PIN proteins. Our studies establish a lipid-dependent phosphorylation cascade connecting membrane composition-based cellular signalling with plant growth and patterning by regulating morphogenetic auxin fluxes.

Alternative splicing and DNA damage response in plants - Nimeth, Barbara Anna; Riegler, Stefan; Kalyna, Maria (Frontiers in Plant Science)
Plants are exposed to a variety of abiotic and biotic stresses that may result in DNA damage. Endogenous processes - such as DNA replication, DNA recombination, respiration, or photosynthesis - are also a threat to DNA integrity. It is therefore essential to understand the strategies plants have developed for DNA damage detection, signaling, and repair. Alternative splicing (AS) is a key post-transcriptional process with a role in regulation of gene expression. Recent studies demonstrate that the majority of intron-containing genes in plants are alternatively spliced, highlighting the importance of AS in plant development and stress response. Not only does AS ensure a versatile proteome and influence the abundance and availability of proteins greatly, it has also emerged as an important player in the DNA damage response (DDR) in animals. Despite extensive studies of DDR carried out in plants, its regulation at the level of AS has not been comprehensively addressed. Here, we provide some insights into the interplay between AS and DDR in plants.

Uncoupling endosomal CLC chloride/proton exchange causes severe neurodegeneration - Weinert, Stefanie; Gimber, Niclas; Deuschel, Dorothea; Stuhlmann, Till; Puchkov, Dmytro; Farsi, Zohreh; Ludwig, Carmen F.; Novarino, Gaia; López-Cayuqueo, Karen I.; Planells-Cases, Rosa; Jentsch, Thomas J. (EMBO Journal)
CLC chloride/proton exchangers may support acidification of endolysosomes and raise their luminal Cl− concentration. Disruption of endosomal ClC‐3 causes severe neurodegeneration. To assess the importance of ClC‐3 Cl−/H+ exchange, we now generate Clcn3unc/unc mice in which ClC‐3 is converted into a Cl− channel. Unlike Clcn3−/− mice, Clcn3unc/unc mice appear normal owing to compensation by ClC‐4 with which ClC‐3 forms heteromers. ClC‐4 protein levels are strongly reduced in Clcn3−/−, but not in Clcn3unc/unc mice because ClC‐3unc binds and stabilizes ClC‐4 like wild‐type ClC‐3. Although mice lacking ClC‐4 appear healthy, its absence in Clcn3unc/unc/Clcn4−/− mice entails even stronger neurodegeneration than observed in Clcn3−/− mice. A fraction of ClC‐3 is found on synaptic vesicles, but miniature postsynaptic currents and synaptic vesicle acidification are not affected in Clcn3unc/unc or Clcn3−/− mice before neurodegeneration sets in. Both, Cl−/H+‐exchange activity and the stabilizing effect on ClC‐4, are central to the biological function of ClC‐3.

Quantum Hellinger distances revisited - Pitrik, Jozsef; Virosztek, Daniel (Letters in Mathematical Physics)
This short note aims to study quantum Hellinger distances investigated recently by Bhatia et al. (Lett Math Phys 109:1777–1804, 2019) with a particular emphasis on barycenters. We introduce the family of generalized quantum Hellinger divergences that are of the form ϕ(A,B)=Tr((1−c)A+cB−AσB), where σ is an arbitrary Kubo–Ando mean, and c∈(0,1) is the weight of σ. We note that these divergences belong to the family of maximal quantum f-divergences, and hence are jointly convex, and satisfy the data processing inequality. We derive a characterization of the barycenter of finitely many positive definite operators for these generalized quantum Hellinger divergences. We note that the characterization of the barycenter as the weighted multivariate 1/2-power mean, that was claimed in Bhatia et al. (2019), is true in the case of commuting operators, but it is not correct in the general case.

Action representation in the mouse parieto-frontal network - Tombaz, Tuce; Dunn, Benjamin A.; Hovde, Karoline; Cubero, Ryan J; Mimica, Bartul; Mamidanna, Pranav; Roudi, Yasser; Whitlock, Jonathan R. (Scientific reports)
The posterior parietal cortex (PPC) and frontal motor areas comprise a cortical network supporting goal-directed behaviour, with functions including sensorimotor transformations and decision making. In primates, this network links performed and observed actions via mirror neurons, which fire both when individuals perform an action and when they observe the same action performed by a conspecific. Mirror neurons are believed to be important for social learning, but it is not known whether mirror-like neurons occur in similar networks in other social species, such as rodents, or if they can be measured in such models using paradigms where observers passively view a demonstrator. Therefore, we imaged Ca2+ responses in PPC and secondary motor cortex (M2) while mice performed and observed pellet-reaching and wheel-running tasks, and found that cell populations in both areas robustly encoded several naturalistic behaviours. However, neural responses to the same set of observed actions were absent, although we verified that observer mice were attentive to performers and that PPC neurons responded reliably to visual cues. Statistical modelling also indicated that executed actions outperformed observed actions in predicting neural responses. These results raise the possibility that sensorimotor action recognition in rodents could take place outside of the parieto-frontal circuit, and underscore that detecting socially-driven neural coding depends critically on the species and behavioural paradigm used.

The IYPT and the 'Ring Oiler' problem - Plesch, Martin; Plesník, Samuel; Ruzickova, Natalia (European Journal of Physics)
The International Young Physicists' Tournament (IYPT) continued in 2018 in Beijing, China and 2019 in Warsaw, Poland with its 31st and 32nd editions. The IYPT is a modern scientific competition for teams of high school students, also known as the Physics World Cup. It involves long-term theoretical and experimental work focused on solving 17 publicly announced open-ended problems in teams of five. On top of that, teams have to present their solutions in front of other teams and a scientific jury, and get opposed and reviewed by their peers. Here we present a brief information about the competition with a specific focus on one of the IYPT 2018 tasks, the 'Ring Oiler'. This seemingly simple mechanical problem appeared to be of such a complexity that even the dozens of participating teams and jurying scientists were not able to solve all of its subtleties.

Exclusive electron transport in Core@Shell PbTe@PbS colloidal semiconductor nanocrystal assemblies - Miranti, Retno; Shin, Daiki; Septianto, Ricky Dwi; Ibáñez, Maria; Kovalenko, Maksym V.; Matsushita, Nobuhiro; Iwasa, Yoshihiro; Bisri, Satria Zulkarnaen (ACS Nano)
Assemblies of colloidal semiconductor nanocrystals (NCs) in the form of thin solid films leverage the size-dependent quantum confinement properties and the wet chemical methods vital for the development of the emerging solution-processable electronics, photonics, and optoelectronics technologies. The ability to control the charge carrier transport in the colloidal NC assemblies is fundamental for altering their electronic and optical properties for the desired applications. Here we demonstrate a strategy to render the solids of narrow-bandgap NC assemblies exclusively electron-transporting by creating a type-II heterojunction via shelling. Electronic transport of molecularly cross-linked PbTe@PbS core@shell NC assemblies is measured using both a conventional solid gate transistor and an electric-double-layer transistor, as well as compared with those of core-only PbTe NCs. In contrast to the ambipolar characteristics demonstrated by many narrow-bandgap NCs, the core@shell NCs exhibit exclusive n-type transport, i.e., drastically suppressed contribution of holes to the overall transport. The PbS shell that forms a type-II heterojunction assists the selective carrier transport by heavy doping of electrons into the PbTe-core conduction level and simultaneously strongly localizes the holes within the NC core valence level. This strongly enhanced n-type transport makes these core@shell NCs suitable for applications where ambipolar characteristics should be actively suppressed, in particular, for thermoelectric and electron-transporting layers in photovoltaic devices.

Modeling adhesion-independent cell migration - Jankowiak, Gaspard; Peurichard, Diane; Reversat, Anne; Schmeiser, Christian; Sixt, Michael K (Mathematical Models and Methods in Applied Sciences)
A two-dimensional mathematical model for cells migrating without adhesion capabilities is presented and analyzed. Cells are represented by their cortex, which is modeled as an elastic curve, subject to an internal pressure force. Net polymerization or depolymerization in the cortex is modeled via local addition or removal of material, driving a cortical flow. The model takes the form of a fully nonlinear degenerate parabolic system. An existence analysis is carried out by adapting ideas from the theory of gradient flows. Numerical simulations show that these simple rules can account for the behavior observed in experiments, suggesting a possible mechanical mechanism for adhesion-independent motility.

Rare earth elements induce cytoskeleton-dependent and PI4P-associated rearrangement of SYT1/SYT5 ER-PM contact site complexes in Arabidopsis - Lee, E; Vila Nova Santana, B; Samuels, E; Benitez-Fuente, F; Corsi, E; Botella, MA; Perez-Sancho, J; Vanneste, S; Friml, Jiří; Macho, A; Alves Azevedo, A; Rosado, A (Journal of Experimental Botany)
In plant cells, environmental stressors promote changes in connectivity between the cortical ER and the PM. Although this process is tightly regulated in space and time, the molecular signals and structural components mediating these changes in inter-organelle communication are only starting to be characterized. In this report, we confirm the presence of a putative tethering complex containing the synaptotagmins 1 and 5 (SYT1 and SYT5) and the Ca2+ and lipid binding protein 1 (CLB1/SYT7). This complex is enriched at ER-PM contact sites (EPCS), have slow responses to changes in extracellular Ca2+, and display severe cytoskeleton-dependent rearrangements in response to the trivalent lanthanum (La3+) and gadolinium (Gd3+) rare earth elements (REEs). Although REEs are generally used as non-selective cation channel blockers at the PM, here we show that the slow internalization of REEs into the cytosol underlies the activation of the Ca2+/Calmodulin intracellular signaling, the accumulation of phosphatidylinositol-4-phosphate (PI4P) at the PM, and the cytoskeleton-dependent rearrangement of the SYT1/SYT5 EPCS complexes. We propose that the observed EPCS rearrangements act as a slow adaptive response to sustained stress conditions, and that this process involves the accumulation of stress-specific phosphoinositides species at the PM.

Clustering of neural activity: A design principle for population codes - Berry, Michael J.; Tkačik, Gašper (Frontiers in Computational Neuroscience)
We propose that correlations among neurons are generically strong enough to organize neural activity patterns into a discrete set of clusters, which can each be viewed as a population codeword. Our reasoning starts with the analysis of retinal ganglion cell data using maximum entropy models, showing that the population is robustly in a frustrated, marginally sub-critical, or glassy, state. This leads to an argument that neural populations in many other brain areas might share this structure. Next, we use latent variable models to show that this glassy state possesses well-defined clusters of neural activity. Clusters have three appealing properties: (i) clusters exhibit error correction, i.e., they are reproducibly elicited by the same stimulus despite variability at the level of constituent neurons; (ii) clusters encode qualitatively different visual features than their constituent neurons; and (iii) clusters can be learned by downstream neural circuits in an unsupervised fashion. We hypothesize that these properties give rise to a “learnable” neural code which the cortical hierarchy uses to extract increasingly complex features without supervision or reinforcement.

Non-equilibrium quantum spin dynamics from classical stochastic processes - De Nicola, Stefano; Doyon, B.; Bhaseen, M. J. (Journal of Statistical Mechanics: Theory and Experiment)
Following on from our recent work, we investigate a stochastic approach to non-equilibrium quantum spin systems. We show how the method can be applied to a variety of physical observables and for different initial conditions. We provide exact formulae of broad applicability for the time-dependence of expectation values and correlation functions following a quantum quench in terms of averages over classical stochastic processes. We further explore the behavior of the classical stochastic variables in the presence of dynamical quantum phase transitions, including results for their distributions and correlation functions. We provide details on the numerical solution of the associated stochastic differential equations, and examine the growth of fluctuations in the classical description. We discuss the strengths and limitations of the current implementation of the stochastic approach and the potential for further development.

From weakly interacting particles to a regularised Dean-Kawasaki model - Cornalba, Federico; Shardlow, Tony; Zimmer, Johannes (Nonlinearity)
The evolution of finitely many particles obeying Langevin dynamics is described by Dean–Kawasaki equations, a class of stochastic equations featuring a non-Lipschitz multiplicative noise in divergence form. We derive a regularised Dean–Kawasaki model based on second order Langevin dynamics by analysing a system of particles interacting via a pairwise potential. Key tools of our analysis are the propagation of chaos and Simon's compactness criterion. The model we obtain is a small-noise stochastic perturbation of the undamped McKean–Vlasov equation. We also provide a high-probability result for existence and uniqueness for our model.

Density of GABAB receptors is reduced in granule cells of the hippocampus in a mouse model of Alzheimer's disease - Martín-Belmonte, Alejandro; Aguado, Carolina; Alfaro-Ruíz, Rocío; Moreno-Martínez, Ana Esther; De La Ossa, Luis; Martínez-Hernández, José; Buisson, Alain; Shigemoto, Ryuichi; Fukazawa, Yugo; Luján, Rafael (International journal of molecular sciences)
Metabotropic γ-aminobutyric acid (GABAB) receptors contribute to the control of network activity and information processing in hippocampal circuits by regulating neuronal excitability and synaptic transmission. The dysfunction in the dentate gyrus (DG) has been implicated in Alzheimer´s disease (AD). Given the involvement of GABAB receptors in AD, to determine their subcellular localisation and possible alteration in granule cells of the DG in a mouse model of AD at 12 months of age, we used high-resolution immunoelectron microscopic analysis. Immunohistochemistry at the light microscopic level showed that the regional and cellular expression pattern of GABAB1 was similar in an AD model mouse expressing mutated human amyloid precursor protein and presenilin1 (APP/PS1) and in age-matched wild type mice. High-resolution immunoelectron microscopy revealed a distance-dependent gradient of immunolabelling for GABAB receptors, increasing from proximal to distal dendrites in both wild type and APP/PS1 mice. However, the overall density of GABAB receptors at the neuronal surface of these postsynaptic compartments of granule cells was significantly reduced in APP/PS1 mice. Parallel to this reduction in surface receptors, we found a significant increase in GABAB1 at cytoplasmic sites. GABAB receptors were also detected at presynaptic sites in the molecular layer of the DG. We also found a decrease in plasma membrane GABAB receptors in axon terminals contacting dendritic spines of granule cells, which was more pronounced in the outer than in the inner molecular layer. Altogether, our data showing post- and presynaptic reduction in surface GABAB receptors in the DG suggest the alteration of the GABAB-mediated modulation of excitability and synaptic transmission in granule cells, which may contribute to the cognitive dysfunctions in the APP/PS1 model of AD

Advantages of acute brain slices prepared at physiological temperature in the characterization of synaptic functions - Eguchi, Kohgaku; Velicky, Philipp; Hollergschwandtner, Elena; Itakura, Makoto; Fukazawa, Yugo; Danzl, Johann G; Shigemoto, Ryuichi (Frontiers in Cellular Neuroscience)
Acute brain slice preparation is a powerful experimental model for investigating the characteristics of synaptic function in the brain. Although brain tissue is usually cut at ice-cold temperature (CT) to facilitate slicing and avoid neuronal damage, exposure to CT causes molecular and architectural changes of synapses. To address these issues, we investigated ultrastructural and electrophysiological features of synapses in mouse acute cerebellar slices prepared at ice-cold and physiological temperature (PT). In the slices prepared at CT, we found significant spine loss and reconstruction, synaptic vesicle rearrangement and decrease in synaptic proteins, all of which were not detected in slices prepared at PT. Consistent with these structural findings, slices prepared at PT showed higher release probability. Furthermore, preparation at PT allows electrophysiological recording immediately after slicing resulting in higher detectability of long-term depression (LTD) after motor learning compared with that at CT. These results indicate substantial advantages of the slice preparation at PT for investigating synaptic functions in different physiological conditions.

Wood deformation leads to rearrangement of molecules at the nanoscale - Felhofer, Martin; Bock, Peter; Singh, Adya; Prats Mateu, Batirtze; Zirbs, Ronald; Gierlinger, Notburga (Nano Letters)
Wood, as the most abundant carbon dioxide storing bioresource, is currently driven beyond its traditional use through creative innovations and nanotechnology. For many properties the micro- and nanostructure plays a crucial role and one key challenge is control and detection of chemical and physical processes in the confined microstructure and nanopores of the wooden cell wall. In this study, correlative Raman and atomic force microscopy show high potential for tracking in situ molecular rearrangement of wood polymers during compression. More water molecules (interpreted as wider cellulose microfibril distances) and disentangling of hemicellulose chains are detected in the opened cell wall regions, whereas an increase of lignin is revealed in the compressed areas. These results support a new more “loose” cell wall model based on flexible lignin nanodomains and advance our knowledge of the molecular reorganization during deformation of wood for optimized processing and utilization.

Tri-partitions and bases of an ordered complex - Edelsbrunner, Herbert; Ölsböck, Katharina (Discrete and Computational Geometry)
Generalizing the decomposition of a connected planar graph into a tree and a dual tree, we prove a combinatorial analog of the classic Helmholtz–Hodge decomposition of a smooth vector field. Specifically, we show that for every polyhedral complex, K, and every dimension, p, there is a partition of the set of p-cells into a maximal p-tree, a maximal p-cotree, and a collection of p-cells whose cardinality is the p-th reduced Betti number of K. Given an ordering of the p-cells, this tri-partition is unique, and it can be computed by a matrix reduction algorithm that also constructs canonical bases of cycle and boundary groups.

Cohomological Hall algebras for Higgs torsion sheaves, moduli of triples and sheaves on surfaces - Minets, Sasha (Selecta Mathematica, New Series)
For any free oriented Borel–Moore homology theory A, we construct an associative product on the A-theory of the stack of Higgs torsion sheaves over a projective curve C. We show that the resulting algebra AHa0C admits a natural shuffle presentation, and prove it is faithful when A is replaced with usual Borel–Moore homology groups. We also introduce moduli spaces of stable triples, heavily inspired by Nakajima quiver varieties, whose A-theory admits an AHa0C-action. These triples can be interpreted as certain sheaves on PC(ωC⊕OC). In particular, we obtain an action of AHa0C on the cohomology of Hilbert schemes of points on T∗C.

Surface and catalyst driven singlet oxygen formation in Li-O2 cells - Samojlov, Aleksej; Schuster, David; Kahr, Jürgen; Freunberger, Stefan Alexander (Electrochimica Acta)
Large overpotentials upon discharge and charge of Li-O2 cells have motivated extensive research into heterogeneous solid electrocatalysts or non-carbon electrodes with the aim to improve rate capability, round-trip efficiency and cycle life. These features are equally governed by parasitic reactions, which are now recognized to be caused by the highly reactive singlet oxygen (1O2). However, the link between the presence of electrocatalysts and 1O2 formation in metal-O2 cells is unknown. Here, we show that, compared to pristine carbon black electrodes, a representative selection of electrocatalysts or non-carbon electrodes (noble metal, transition metal compounds) may both slightly reduce or severely increase the 1O2 formation. The individual reaction steps, where the surfaces impact the 1O2 yield are deciphered, showing that 1O2 yield from superoxide disproportionation as well as the decomposition of trace H2O2 are sensitive to catalysts. Transition metal compounds in general are prone to increase 1O2.

Assembly-specific disruption of hippocampal replay leads to selective memory deficit - Gridchyn, Igor; Schönenberger, Philipp; O'Neill, Joseph; Csicsvari, Jozsef L (Neuron)

Neo-gibberellin signaling: Guiding the next generation of the green revolution - Xue, Huidan; Zhang, Yuzhou; Xiao, Guanghui (Trends in Plant Science)
The agricultural green revolution spectacularly enhanced crop yield and lodging resistance with modified DELLA-mediated gibberellin signaling. However, this was achieved at the expense of reduced nitrogen-use efficiency (NUE). Recently, Wu et al. revealed novel gibberellin signaling that provides a blueprint for improving tillering and NUE in Green Revolution varieties (GRVs).

NDUFS4 deletion triggers loss of NDUFA12 in Ndufs4−/− mice and Leigh syndrome patients: A stabilizing role for NDUFAF2 - Adjobo-Hermans, Merel J.W.; De Haas, Ria; Willems, Peter H.G.M.; Wojtala, Aleksandra; Van Emst-De Vries, Sjenet E.; Wagenaars, Jori A.; Van Den Brand, Mariel; Rodenburg, Richard J.; Smeitink, Jan A.M.; Nijtmans, Leo G.; Sazanov, Leonid A; Wieckowski, Mariusz R.; et al. (Biochimica et Biophysica Acta - Bioenergetics)
Mutations in NDUFS4, which encodes an accessory subunit of mitochondrial oxidative phosphorylation (OXPHOS) complex I (CI), induce Leigh syndrome (LS). LS is a poorly understood pediatric disorder featuring brain-specific anomalies and early death. To study the LS pathomechanism, we here compared OXPHOS proteomes between various Ndufs4−/− mouse tissues. Ndufs4−/− animals displayed significantly lower CI subunit levels in brain/diaphragm relative to other tissues (liver/heart/kidney/skeletal muscle), whereas other OXPHOS subunit levels were not reduced. Absence of NDUFS4 induced near complete absence of the NDUFA12 accessory subunit, a 50% reduction in other CI subunit levels, and an increase in specific CI assembly factors. Among the latter, NDUFAF2 was most highly increased. Regarding NDUFS4, NDUFA12 and NDUFAF2, identical results were obtained in Ndufs4−/− mouse embryonic fibroblasts (MEFs) and NDUFS4-mutated LS patient cells. Ndufs4−/− MEFs contained active CI in situ but blue-native-PAGE highlighted that NDUFAF2 attached to an inactive CI subcomplex (CI-830) and inactive assemblies of higher MW. In NDUFA12-mutated LS patient cells, NDUFA12 absence did not reduce NDUFS4 levels but triggered NDUFAF2 association to active CI. BN-PAGE revealed no such association in LS patient fibroblasts with mutations in other CI subunit-encoding genes where NDUFAF2 was attached to CI-830 (NDUFS1, NDUFV1 mutation) or not detected (NDUFS7 mutation). Supported by enzymological and CI in silico structural analysis, we conclude that absence of NDUFS4 induces near complete absence of NDUFA12 but not vice versa, and that NDUFAF2 stabilizes active CI in Ndufs4−/− mice and LS patient cells, perhaps in concert with mitochondrial inner membrane lipids.

Defining the design principles of skin epidermis postnatal growth - Dekoninck, Sophie; Hannezo, Edouard B; Sifrim, Alejandro; Miroshnikova, Yekaterina A.; Aragona, Mariaceleste; Malfait, Milan; Gargouri, Souhir; De Neunheuser, Charlotte; Dubois, Christine; Voet, Thierry; Wickström, Sara A.; Simons, Benjamin D.; et al. (Cell)
During embryonic and postnatal development, organs and tissues grow steadily to achieve their final size at the end of puberty. However, little is known about the cellular dynamics that mediate postnatal growth. By combining in vivo clonal lineage tracing, proliferation kinetics, single-cell transcriptomics, andin vitro micro-pattern experiments, we resolved the cellular dynamics taking place during postnatal skin epidermis expansion. Our data revealed that harmonious growth is engineered by a single population of developmental progenitors presenting a fixed fate imbalance of self-renewing divisions with an ever-decreasing proliferation rate. Single-cell RNA sequencing revealed that epidermal developmental progenitors form a more uniform population compared with adult stem and progenitor cells. Finally, we found that the spatial pattern of cell division orientation is dictated locally by the underlying collagen fiber orientation. Our results uncover a simple design principle of organ growth where progenitors and differentiated cells expand in harmony with their surrounding tissues.

Direct ETTIN-auxin interaction controls chromatin states in gynoecium development - Kuhn, André; Ramans Harborough, Sigurd; McLaughlin, Heather M; Natarajan, Bhavani; Verstraeten, Inge; Friml, Jiří; Kepinski, Stefan; Østergaard, Lars (eLife)
Hormonal signalling in animals often involves direct transcription factor-hormone interactions that modulate gene expression. In contrast, plant hormone signalling is most commonly based on de-repression via the degradation of transcriptional repressors. Recently, we uncovered a non-canonical signalling mechanism for the plant hormone auxin whereby auxin directly affects the activity of the atypical auxin response factor (ARF), ETTIN towards target genes without the requirement for protein degradation. Here we show that ETTIN directly binds auxin, leading to dissociation from co-repressor proteins of the TOPLESS/TOPLESS-RELATED family followed by histone acetylation and induction of gene expression. This mechanism is reminiscent of animal hormone signalling as it affects the activity towards regulation of target genes and provides the first example of a DNA-bound hormone receptor in plants. Whilst auxin affects canonical ARFs indirectly by facilitating degradation of Aux/IAA repressors, direct ETTIN-auxin interactions allow switching between repressive and de-repressive chromatin states in an instantly-reversible manner.

The free energy of the two-dimensional dilute Bose gas. I. Lower bound - Deuchert, Andreas; Mayer, Simon; Seiringer, Robert (Forum of Mathematics, Sigma)
We prove a lower bound for the free energy (per unit volume) of the two-dimensional Bose gas in the thermodynamic limit. We show that the free energy at density 𝜌 and inverse temperature 𝛽 differs from the one of the noninteracting system by the correction term 𝜋𝜌𝜌𝛽𝛽 . Here, is the scattering length of the interaction potential, and 𝛽 is the inverse Berezinskii–Kosterlitz–Thouless critical temperature for superfluidity. The result is valid in the dilute limit 𝜌 and if 𝛽𝜌 .

Broad spectral tuning of ultra-low-loss polaritons in a van der Waals crystal by intercalation - Taboada-Gutiérrez, Javier; Álvarez-Pérez, Gonzalo; Duan, Jiahua; Ma, Weiliang; Crowley, Kyle; Prieto Gonzalez, Ivan; Bylinkin, Andrei; Autore, Marta; Volkova, Halyna; Kimura, Kenta; Kimura, Tsuyoshi; Berger, M. H.; et al. (Nature Materials)
Phonon polaritons—light coupled to lattice vibrations—in polar van der Waals crystals are promising candidates for controlling the flow of energy on the nanoscale due to their strong field confinement, anisotropic propagation and ultra-long lifetime in the picosecond range1,2,3,4,5. However, the lack of tunability of their narrow and material-specific spectral range—the Reststrahlen band—severely limits their technological implementation. Here, we demonstrate that intercalation of Na atoms in the van der Waals semiconductor α-V2O5 enables a broad spectral shift of Reststrahlen bands, and that the phonon polaritons excited show ultra-low losses (lifetime of 4 ± 1 ps), similar to phonon polaritons in a non-intercalated crystal (lifetime of 6 ± 1 ps). We expect our intercalation method to be applicable to other van der Waals crystals, opening the door for the use of phonon polaritons in broad spectral bands in the mid-infrared domain.

Synergistic on Auxin and Cytokinin 1 positively regulates growth and attenuates soil pathogen resistance - Hurny, Andrej; Cuesta, Candela; Cavallari, Nicola; Ötvös, Krisztina; Duclercq, Jerome; Dokládal, Ladislav; Montesinos López, Juan C; Gallemi, Marçal; Semeradova, Hana; Rauter, Thomas; Stenzel, Irene; Persiau, Geert; et al. (Nature Communications)
Plants as non-mobile organisms constantly integrate varying environmental signals to flexibly adapt their growth and development. Local fluctuations in water and nutrient availability, sudden changes in temperature or other abiotic and biotic stresses can trigger changes in the growth of plant organs. Multiple mutually interconnected hormonal signaling cascades act as essential endogenous translators of these exogenous signals in the adaptive responses of plants. Although the molecular backbones of hormone transduction pathways have been identified, the mechanisms underlying their interactions are largely unknown. Here, using genome wide transcriptome profiling we identify an auxin and cytokinin cross-talk component; SYNERGISTIC ON AUXIN AND CYTOKININ 1 (SYAC1), whose expression in roots is strictly dependent on both of these hormonal pathways. We show that SYAC1 is a regulator of secretory pathway, whose enhanced activity interferes with deposition of cell wall components and can fine-tune organ growth and sensitivity to soil pathogens.

Clusters in separated tubes of tilted dipoles - Armstrong, Jeremy R.; Jensen, Aksel S.; Volosniev, Artem; Zinner, Nikolaj T. (Mathematics)
A few-body cluster is a building block of a many-body system in a gas phase provided the temperature at most is of the order of the binding energy of this cluster. Here we illustrate this statement by considering a system of tubes filled with dipolar distinguishable particles. We calculate the partition function, which determines the probability to find a few-body cluster at a given temperature. The input for our calculations—the energies of few-body clusters—is estimated using the harmonic approximation. We first describe and demonstrate the validity of our numerical procedure. Then we discuss the results featuring melting of the zero-temperature many-body state into a gas of free particles and few-body clusters. For temperature higher than its binding energy threshold, the dimers overwhelmingly dominate the ensemble, where the remaining probability is in free particles. At very high temperatures free (harmonic oscillator trap-bound) particle dominance is eventually reached. This structure evolution appears both for one and two particles in each layer providing crucial information about the behavior of ultracold dipolar gases. The investigation addresses the transition region between few- and many-body physics as a function of temperature using a system of ten dipoles in five tubes.

MALT-1 mediates IL-17 neural signaling to regulate C. elegans behavior, immunity and longevity - Flynn, Sean M.; Chen, Changchun; Artan, Murat; Barratt, Stephen; Crisp, Alastair; Nelson, Geoffrey M.; Peak-Chew, Sew Yeu; Begum, Farida; Skehel, Mark; De Bono, Mario (Nature Communications)
Besides pro-inflammatory roles, the ancient cytokine interleukin-17 (IL-17) modulates neural circuit function. We investigate IL-17 signaling in neurons, and the extent it can alter organismal phenotypes. We combine immunoprecipitation and mass spectrometry to biochemically characterize endogenous signaling complexes that function downstream of IL-17 receptors in C. elegans neurons. We identify the paracaspase MALT-1 as a critical output of the pathway. MALT1 mediates signaling from many immune receptors in mammals, but was not previously implicated in IL-17 signaling or nervous system function. C. elegans MALT-1 forms a complex with homologs of Act1 and IRAK and appears to function both as a scaffold and a protease. MALT-1 is expressed broadly in the C. elegans nervous system, and neuronal IL-17–MALT-1 signaling regulates multiple phenotypes, including escape behavior, associative learning, immunity and longevity. Our data suggest MALT1 has an ancient role modulating neural circuit function downstream of IL-17 to remodel physiology and behavior.

Microtubules control cellular shape and coherence in amoeboid migrating cells - Kopf, Aglaja; Renkawitz, Jörg; Hauschild, Robert; Girkontaite, Irute; Tedford, Kerry; Merrin, Jack; Thorn-Seshold, Oliver; Trauner, Dirk; Häcker, Hans; Fischer, Klaus Dieter; Kiermaier, Eva; Sixt, Michael K (The Journal of Cell Biology)
Cells navigating through complex tissues face a fundamental challenge: while multiple protrusions explore different paths, the cell needs to avoid entanglement. How a cell surveys and then corrects its own shape is poorly understood. Here, we demonstrate that spatially distinct microtubule dynamics regulate amoeboid cell migration by locally promoting the retraction of protrusions. In migrating dendritic cells, local microtubule depolymerization within protrusions remote from the microtubule organizing center triggers actomyosin contractility controlled by RhoA and its exchange factor Lfc. Depletion of Lfc leads to aberrant myosin localization, thereby causing two effects that rate-limit locomotion: (1) impaired cell edge coordination during path finding and (2) defective adhesion resolution. Compromised shape control is particularly hindering in geometrically complex microenvironments, where it leads to entanglement and ultimately fragmentation of the cell body. We thus demonstrate that microtubules can act as a proprioceptive device: they sense cell shape and control actomyosin retraction to sustain cellular coherence.

MAU2 and NIPBL variants impair the heterodimerization of the cohesin loader subunits and cause Cornelia de Lange syndrome - Parenti, Ilaria; Diab, Farah; Gil, Sara Ruiz; Mulugeta, Eskeatnaf; Casa, Valentina; Berutti, Riccardo; Brouwer, Rutger W.W.; Dupé, Valerie; Eckhold, Juliane; Graf, Elisabeth; Puisac, Beatriz; Ramos, Feliciano; et al. (Cell Reports)
The NIPBL/MAU2 heterodimer loads cohesin onto chromatin. Mutations inNIPBLaccount for most cases ofthe rare developmental disorder Cornelia de Lange syndrome (CdLS). Here we report aMAU2 variant causing CdLS, a deletion of seven amino acids that impairs the interaction between MAU2 and the NIPBL N terminus.Investigating this interaction, we discovered that MAU2 and the NIPBL N terminus are largely dispensable fornormal cohesin and NIPBL function in cells with a NIPBL early truncating mutation. Despite a predicted fataloutcome of an out-of-frame single nucleotide duplication inNIPBL, engineered in two different cell lines,alternative translation initiation yields a form of NIPBL missing N-terminal residues. This form cannot interactwith MAU2, but binds DNA and mediates cohesin loading. Altogether, our work reveals that cohesin loading can occur independently of functional NIPBL/MAU2 complexes and highlights a novel mechanism protectiveagainst out-of-frame mutations that is potentially relevant for other genetic conditions.

Synergism of type 1 metabotropic and ionotropic glutamate receptors in cerebellar molecular layer interneurons in vivo - Bao, Jin; Graupner, Michael; Astorga, Guadalupe; Collin, Thibault; Jalil, Abdelali; Indriati, Dwi Wahyu; Bradley, Jonathan; Shigemoto, Ryuichi; Llano, Isabel (eLife)
Type 1 metabotropic glutamate receptors (mGluR1s) are key elements in neuronal signaling. While their function is well documented in slices, requirements for their activation in vivo are poorly understood. We examine this question in adult mice in vivo using 2-photon imaging of cerebellar molecular layer interneurons (MLIs) expressing GCaMP. In anesthetized mice, parallel fiber activation evokes beam-like Cai rises in postsynaptic MLIs which depend on co-activation of mGluR1s and ionotropic glutamate receptors (iGluRs). In awake mice, blocking mGluR1 decreases Cai rises associated with locomotion. In vitro studies and freeze-fracture electron microscopy show that the iGluR-mGluR1 interaction is synergistic and favored by close association of the two classes of receptors. Altogether our results suggest that mGluR1s, acting in synergy with iGluRs, potently contribute to processing cerebellar neuronal signaling under physiological conditions.

Dopamine transporter trafficking and Rit2 GTPase: Mechanism of action and in vivo impact - Fagan, Rita R.; Kearney, Patrick J.; Sweeney, Carolyn G.; Luethi, Dino; Schoot Uiterkamp, Florianne E; Schicker, Klaus; Alejandro, Brian S.; O'Connor, Lauren C.; Sitte, Harald H.; Melikian, Haley E. (Journal of Biological Chemistry)
Following its evoked release, dopamine (DA) signaling is rapidly terminated by presynaptic reuptake, mediated by the cocaine-sensitive DA transporter (DAT). DAT surface availability is dynamically regulated by endocytic trafficking, and direct protein kinase C (PKC) activation acutely diminishes DAT surface expression by accelerating DAT internalization. Previous cell line studies demonstrated that PKC-stimulated DAT endocytosis requires both Ack1 inactivation, which releases a DAT-specific endocytic brake, and the neuronal GTPase, Rit2, which binds DAT. However, it is unknown whether Rit2 is required for PKC-stimulated DAT endocytosis in DAergic terminals or whether there are region- and/or sex-dependent differences in PKC-stimulated DAT trafficking. Moreover, the mechanisms by which Rit2 controls PKC-stimulated DAT endocytosis are unknown. Here, we directly examined these important questions. Ex vivo studies revealed that PKC activation acutely decreased DAT surface expression selectively in ventral, but not dorsal, striatum. AAV-mediated, conditional Rit2 knockdown in DAergic neurons impacted baseline DAT surface:intracellular distribution in DAergic terminals from female ventral, but not dorsal, striatum. Further, Rit2 was required for PKC-stimulated DAT internalization in both male and female ventral striatum. FRET and surface pulldown studies in cell lines revealed that PKC activation drives DAT-Rit2 surface dissociation and that the DAT N terminus is required for both PKC-mediated DAT-Rit2 dissociation and DAT internalization. Finally, we found that Rit2 and Ack1 independently converge on DAT to facilitate PKC-stimulated DAT endocytosis. Together, our data provide greater insight into mechanisms that mediate PKC-regulated DAT internalization and reveal unexpected region-specific differences in PKC-stimulated DAT trafficking in bona fide DAergic terminals.

Precision medicine in clinical oncology: the journey from IgG antibody to IgE - Singer, Judit; Singer, Josef; Jensen-Jarolim, Erika (Current opinion in allergy and clinical immunology)
Purpose of review: Cancer is one of the leading causes of death and the incidence rates are constantly rising. The heterogeneity of tumors poses a big challenge for the treatment of the disease and natural antibodies additionally affect disease progression. The introduction of engineered mAbs for anticancer immunotherapies has substantially improved progression-free and overall survival of cancer patients, but little efforts have been made to exploit other antibody isotypes than IgG. Recent findings: In order to improve these therapies, ‘next-generation antibodies’ were engineered to enhance a specific feature of classical antibodies and form a group of highly effective and precise therapy compounds. Advanced antibody approaches include among others antibody-drug conjugates, glyco-engineered and Fc-engineered antibodies, antibody fragments, radioimmunotherapy compounds, bispecific antibodies and alternative (non-IgG) immunoglobulin classes, especially IgE. Summary: The current review describes solutions for the needs of next-generation antibody therapies through different approaches. Careful selection of the best-suited engineering methodology is a key factor in developing personalized, more specific and more efficient mAbs against cancer to improve the outcomes of cancer patients. We highlight here the large evidence of IgE exploiting a highly cytotoxic effector arm as potential next-generation anticancer immunotherapy.

T cells: Bridge-and-channel commute to the white pulp - Sixt, Michael K; Lämmermann, Tim (Immunity)
In contrast to lymph nodes, the lymphoid regions of the spleen—the white pulp—are located deep within the organ, yielding the trafficking paths of T cells in the white pulp largely invisible. In an intravital microscopy tour de force reported in this issue of Immunity, Chauveau et al. show that T cells perform unidirectional, perivascular migration through the enigmatic marginal zone bridging channels.

Loss of Ena/VASP interferes with lamellipodium architecture, motility and integrin-dependent adhesion - Damiano-Guercio, Julia; Kurzawa, Laëtitia; Müller, Jan; Dimchev, Georgi A; Schaks, Matthias; Nemethova, Maria; Pokrant, Thomas; Brühmann, Stefan; Linkner, Joern; Blanchoin, Laurent; Sixt, Michael K; Rottner, Klemens; et al. (eLife)
Cell migration entails networks and bundles of actin filaments termed lamellipodia and microspikes or filopodia, respectively, as well as focal adhesions, all of which recruit Ena/VASP family members hitherto thought to antagonize efficient cell motility. However, we find these proteins to act as positive regulators of migration in different murine cell lines. CRISPR/Cas9-mediated loss of Ena/VASP proteins reduced lamellipodial actin assembly and perturbed lamellipodial architecture, as evidenced by changed network geometry as well as reduction of filament length and number that was accompanied by abnormal Arp2/3 complex and heterodimeric capping protein accumulation. Loss of Ena/VASP function also abolished the formation of microspikes normally embedded in lamellipodia, but not of filopodia capable of emanating without lamellipodia. Ena/VASP-deficiency also impaired integrin-mediated adhesion accompanied by reduced traction forces exerted through these structures. Our data thus uncover novel Ena/VASP functions of these actin polymerases that are fully consistent with their promotion of cell migration.

Frequency-dependent block of excitatory neurotransmission by isoflurane via dual presynaptic mechanisms - Wang, Han Ying; Eguchi, Kohgaku; Yamashita, Takayuki; Takahashi, Tomoyuki (Journal of Neuroscience)
Volatile anesthetics are widely used for surgery, but neuronal mechanisms of anesthesia remain unidentified. At the calyx of Held in brainstem slices from rats of either sex, isoflurane at clinical doses attenuated EPSCs by decreasing the release probability and the number of readily releasable vesicles. In presynaptic recordings of Ca2+ currents and exocytic capacitance changes, isoflurane attenuated exocytosis by inhibiting Ca2+ currents evoked by a short presynaptic depolarization, whereas it inhibited exocytosis evoked by a prolonged depolarization via directly blocking exocytic machinery downstream of Ca2+ influx. Since the length of presynaptic depolarization can simulate the frequency of synaptic inputs, isoflurane anesthesia is likely mediated by distinct dual mechanisms, depending on input frequencies. In simultaneous presynaptic and postsynaptic action potential recordings, isoflurane impaired the fidelity of repetitive spike transmission, more strongly at higher frequencies. Furthermore, in the cerebrum of adult mice, isoflurane inhibited monosynaptic corticocortical spike transmission, preferentially at a higher frequency. We conclude that dual presynaptic mechanisms operate for the anesthetic action of isoflurane, of which direct inhibition of exocytic machinery plays a low-pass filtering role in spike transmission at central excitatory synapses.

A method for identification of the methylation level of CpG islands from NGS data - Uroshlev, Leonid A.; Abdullaev, Eldar T.; Umarova, Iren R.; Il’Icheva, Irina A.; Panchenko, Larisa A.; Polozov, Robert V.; Kondrashov, Fyodor; Nechipurenko, Yury D.; Grokhovsky, Sergei L. (Scientific Reports)
In the course of sample preparation for Next Generation Sequencing (NGS), DNA is fragmented by various methods. Fragmentation shows a persistent bias with regard to the cleavage rates of various dinucleotides. With the exception of CpG dinucleotides the previously described biases were consistent with results of the DNA cleavage in solution. Here we computed cleavage rates of all dinucleotides including the methylated CpG and unmethylated CpG dinucleotides using data of the Whole Genome Sequencing datasets of the 1000 Genomes project. We found that the cleavage rate of CpG is significantly higher for the methylated CpG dinucleotides. Using this information, we developed a classifier for distinguishing cancer and healthy tissues based on their CpG islands statuses of the fragmentation. A simple Support Vector Machine classifier based on this algorithm shows an accuracy of 84%. The proposed method allows the detection of epigenetic markers purely based on mechanochemical DNA fragmentation, which can be detected by a simple analysis of the NGS sequencing data.

Synthetic spin-orbit coupling mediated by a bosonic environment - Maslov, Mikhail; Lemeshko, Mikhail; Yakaboylu, Enderalp (Physical Review B)
We study a mobile quantum impurity, possessing internal rotational degrees of freedom, confined to a ring in the presence of a many-particle bosonic bath. By considering the recently introduced rotating polaron problem, we define the Hamiltonian and examine the energy spectrum. The weak-coupling regime is studied by means of a variational ansatz in the truncated Fock space. The corresponding spectrum indicates that there emerges a coupling between the internal and orbital angular momenta of the impurity as a consequence of the phonon exchange. We interpret the coupling as a phonon-mediated spin-orbit coupling and quantify it by using a correlation function between the internal and the orbital angular momentum operators. The strong-coupling regime is investigated within the Pekar approach, and it is shown that the correlation function of the ground state shows a kink at a critical coupling, that is explained by a sharp transition from the noninteracting state to the states that exhibit strong interaction with the surroundings. The results might find applications in such fields as spintronics or topological insulators where spin-orbit coupling is of crucial importance.

Hard antinodal gap revealed by quantum oscillations in the pseudogap regime of underdoped high-Tc superconductors - Hartstein, Máté; Hsu, Yu Te; Modic, Kimberly A; Porras, Juan; Loew, Toshinao; Tacon, Matthieu Le; Zuo, Huakun; Wang, Jinhua; Zhu, Zengwei; Chan, Mun K.; Mcdonald, Ross D.; Lonzarich, Gilbert G.; et al. (Nature Physics)
An understanding of the missing antinodal electronic excitations in the pseudogap state is essential for uncovering the physics of the underdoped cuprate high-temperature superconductors1,2,3,4,5,6. The majority of high-temperature experiments performed thus far, however, have been unable to discern whether the antinodal states are rendered unobservable due to their damping or whether they vanish due to their gapping7,8,9,10,11,12,13,14,15,16,17,18. Here, we distinguish between these two scenarios by using quantum oscillations to examine whether the small Fermi surface pocket, found to occupy only 2% of the Brillouin zone in the underdoped cuprates19,20,21,22,23,24, exists in isolation against a majority of completely gapped density of states spanning the antinodes, or whether it is thermodynamically coupled to a background of ungapped antinodal states. We find that quantum oscillations associated with the small Fermi surface pocket exhibit a signature sawtooth waveform characteristic of an isolated two-dimensional Fermi surface pocket25,26,27,28,29,30,31,32. This finding reveals that the antinodal states are destroyed by a hard gap that extends over the majority of the Brillouin zone, placing strong constraints on a drastic underlying origin of quasiparticle disappearance over almost the entire Brillouin zone in the pseudogap regime7,8,9,10,11,12,13,14,15,16,17,18.

The Arabidopsis NRT1.1 transceptor coordinately controls auxin biosynthesis and transport to regulate root branching in response to nitrate - Maghiaoui, A; Bouguyon, E; Cuesta, Candela; Perrine-Walker, F; Alcon, C; Krouk, G; Benková, Eva; Nacry, P; Gojon, A; Bach, L (Journal of Experimental Botany)
In agricultural systems, nitrate is the main source of nitrogen available for plants. Besides its role as a nutrient, nitrate has been shown to act as a signal molecule for plant growth, development and stress responses. In Arabidopsis, the NRT1.1 nitrate transceptor represses lateral root (LR) development at low nitrate availability by promoting auxin basipetal transport out of the LR primordia (LRPs). In addition, our present study shows that NRT1.1 acts as a negative regulator of the TAR2 auxin biosynthetic gene expression in the root stele. This is expected to repress local auxin biosynthesis and thus to reduce acropetal auxin supply to the LRPs. Moreover, NRT1.1 also negatively affects expression of the LAX3 auxin influx carrier, thus preventing cell wall remodeling required for overlying tissues separation during LRP emergence. Both NRT1.1-mediated repression of TAR2 and LAX3 are suppressed at high nitrate availability, resulting in the nitrate induction of TAR2 and LAX3 expression that is required for optimal stimulation of LR development by nitrate. Altogether, our results indicate that the NRT1.1 transceptor coordinately controls several crucial auxin-associated processes required for LRP development, and as a consequence that NRT1.1 plays a much more integrated role than previously anticipated in regulating the nitrate response of root system architecture.

The PBW theorem for affine Yangians - Yang, Yaping; Zhao, Gufang (Transformation Groups)
We prove that the Yangian associated to an untwisted symmetric affine Kac–Moody Lie algebra is isomorphic to the Drinfeld double of a shuffle algebra. The latter is constructed in [YZ14] as an algebraic formalism of cohomological Hall algebras. As a consequence, we obtain the Poincare–Birkhoff–Witt (PBW) theorem for this class of affine Yangians. Another independent proof of the PBW theorem is given recently by Guay, Regelskis, and Wendlandt [GRW18].

Accompanying dataset for 'Hard antinodal gap revealed by quantum oscillations in the pseudogap regime of underdoped high-Tc superconductors' - Hartstein, Mate; Hsu, Yu-Te; Modic, Kimberly A; Porras, Juan; Loew, Toshinao; Le Tacon, Matthieu; Zuo, Huakun; Wang, Jinhua; Zhu, Zengwei; Chan, Mun; McDonald, Ross; Lonzarich, Gilbert; et al.
This research data supports 'Hard antinodal gap revealed by quantum oscillations in the pseudogap regime of underdoped high-Tc superconductors'. A Readme file for plotting each figure is provided.

Approximating values of generalized-reachability stochastic games - Ashok, Pranav; Chatterjee, Krishnendu; Kretinsky, Jan; Weininger, Maximilian; Winkler, Tobias (Proceedings of the 35th Annual ACM/IEEE Symposium on Logic in Computer Science)
Simple stochastic games are turn-based 2½-player games with a reachability objective. The basic question asks whether one player can ensure reaching a given target with at least a given probability. A natural extension is games with a conjunction of such conditions as objective. Despite a plethora of recent results on the analysis of systems with multiple objectives, the decidability of this basic problem remains open. In this paper, we present an algorithm approximating the Pareto frontier of the achievable values to a given precision. Moreover, it is an anytime algorithm, meaning it can be stopped at any time returning the current approximation and its error bound.

Neurodevelopmental disorders: From genetics to functional pathways - Parenti, Ilaria; Garcia Rabaneda, Luis E; Schön, Hanna; Novarino, Gaia (Trends in Neurosciences)
Neurodevelopmental disorders (NDDs) are a class of disorders affecting brain development and function and are characterized by wide genetic and clinical variability. In this review, we discuss the multiple factors that influence the clinical presentation of NDDs, with particular attention to gene vulnerability, mutational load, and the two-hit model. Despite the complex architecture of mutational events associated with NDDs, the various proteins involved appear to converge on common pathways, such as synaptic plasticity/function, chromatin remodelers and the mammalian target of rapamycin (mTOR) pathway. A thorough understanding of the mechanisms behind these pathways will hopefully lead to the identification of candidates that could be targeted for treatment approaches.

Intersection patterns of planar sets - Kalai, Gil; Patakova, Zuzana (Discrete and Computational Geometry)
Let A={A1,…,An} be a family of sets in the plane. For 0≤i<n, denote by fi the number of subsets σ of {1,…,n} of cardinality i+1 that satisfy ⋂i∈σAi≠∅. Let k≥2 be an integer. We prove that if each k-wise and (k+1)-wise intersection of sets from A is empty, or a single point, or both open and path-connected, then fk+1=0 implies fk≤cfk−1 for some positive constant c depending only on k. Similarly, let b≥2, k>2b be integers. We prove that if each k-wise or (k+1)-wise intersection of sets from A has at most b path-connected components, which all are open, then fk+1=0 implies fk≤cfk−1 for some positive constant c depending only on b and k. These results also extend to two-dimensional compact surfaces.

Almost all string graphs are intersection graphs of plane convex sets - Pach, János; Reed, Bruce; Yuditsky, Yelena (Discrete and Computational Geometry)
A string graph is the intersection graph of a family of continuous arcs in the plane. The intersection graph of a family of plane convex sets is a string graph, but not all string graphs can be obtained in this way. We prove the following structure theorem conjectured by Janson and Uzzell: The vertex set of almost all string graphs on n vertices can be partitioned into five cliques such that some pair of them is not connected by any edge (n→∞). We also show that every graph with the above property is an intersection graph of plane convex sets. As a corollary, we obtain that almost all string graphs on n vertices are intersection graphs of plane convex sets.

Bayesian reassessment of the epigenetic architecture of complex traits - Trejo Banos, D; McCartney, DL; Patxot, M; Anchieri, L; Battram, T; Christiansen, C; Costeira, R; Walker, RM; Morris, SW; Campbell, A; Zhang, Q; Porteous, DJ; et al. (Nature Communications)
Linking epigenetic marks to clinical outcomes improves insight into molecular processes, disease prediction, and therapeutic target identification. Here, a statistical approach is presented to infer the epigenetic architecture of complex disease, determine the variation captured by epigenetic effects, and estimate phenotype-epigenetic probe associations jointly. Implicitly adjusting for probe correlations, data structure (cell-count or relatedness), and single-nucleotide polymorphism (SNP) marker effects, improves association estimates and in 9,448 individuals, 75.7% (95% CI 71.70–79.3) of body mass index (BMI) variation and 45.6% (95% CI 37.3–51.9) of cigarette consumption variation was captured by whole blood methylation array data. Pathway-linked probes of blood cholesterol, lipid transport and sterol metabolism for BMI, and xenobiotic stimuli response for smoking, showed >1.5 times larger associations with >95% posterior inclusion probability. Prediction accuracy improved by 28.7% for BMI and 10.2% for smoking over a LASSO model, with age-, and tissue-specificity, implying associations are a phenotypic consequence rather than causal.

Assortative mating, sexual selection, and their consequences for gene flow in Littorina - Perini, Samuel; Rafajlović, Marina; Westram, Anja M; Johannesson, Kerstin; Butlin, Roger K. (Evolution)
When divergent populations are connected by gene flow, the establishment of complete reproductive isolation usually requires the joint action of multiple barrier effects. One example where multiple barrier effects are coupled consists of a single trait that is under divergent natural selection and also mediates assortative mating. Such multiple‐effect traits can strongly reduce gene flow. However, there are few cases where patterns of assortative mating have been described quantitatively and their impact on gene flow has been determined. Two ecotypes of the coastal marine snail, Littorina saxatilis , occur in North Atlantic rocky‐shore habitats dominated by either crab predation or wave action. There is evidence for divergent natural selection acting on size, and size‐assortative mating has previously been documented. Here, we analyze the mating pattern in L. saxatilis with respect to size in intensively sampled transects across boundaries between the habitats. We show that the mating pattern is mostly conserved between ecotypes and that it generates both assortment and directional sexual selection for small male size. Using simulations, we show that the mating pattern can contribute to reproductive isolation between ecotypes but the barrier to gene flow is likely strengthened more by sexual selection than by assortment.

Data from: Assortative mating, sexual selection and their consequences for gene flow in Littorina - Perini, Samuel; Rafajlovic, Marina; Westram, Anja M; Johannesson, Kerstin; Butlin, Roger
When divergent populations are connected by gene flow, the establishment of complete reproductive isolation usually requires the joint action of multiple barrier effects. One example where multiple barrier effects are coupled consists of a single trait that is under divergent natural selection and also mediates assortative mating. Such multiple-effect traits can strongly reduce gene flow. However, there are few cases where patterns of assortative mating have been described quantitatively and their impact on gene flow has been determined. Two ecotypes of the coastal marine snail, Littorina saxatilis, occur in North Atlantic rocky-shore habitats dominated by either crab predation or wave action. There is evidence for divergent natural selection acting on size, and size-assortative mating has previously been documented. Here, we analyze the mating pattern in L. saxatilis with respect to size in intensively-sampled transects across boundaries between the habitats. We show that the mating pattern is mostly conserved between ecotypes and that it generates both assortment and directional sexual selection for small male size. Using simulations, we show that the mating pattern can contribute to reproductive isolation between ecotypes but the barrier to gene flow is likely strengthened more by sexual selection than by assortment.

Short-term plasticity at hippocampal mossy fiber synapses is induced by natural activity patterns and associated with vesicle pool engram formation - Vandael, David H; Borges Merjane, Carolina; Zhang, Xiaomin; Jonas, Peter M (Neuron)
Post-tetanic potentiation (PTP) is an attractive candidate mechanism for hippocampus-dependent short-term memory. Although PTP has a uniquely large magnitude at hippocampal mossy fiber-CA3 pyramidal neuron synapses, it is unclear whether it can be induced by natural activity and whether its lifetime is sufficient to support short-term memory. We combined in vivo recordings from granule cells (GCs), in vitro paired recordings from mossy fiber terminals and postsynaptic CA3 neurons, and “flash and freeze” electron microscopy. PTP was induced at single synapses and showed a low induction threshold adapted to sparse GC activity in vivo. PTP was mainly generated by enlargement of the readily releasable pool of synaptic vesicles, allowing multiplicative interaction with other plasticity forms. PTP was associated with an increase in the docked vesicle pool, suggesting formation of structural “pool engrams.” Absence of presynaptic activity extended the lifetime of the potentiation, enabling prolonged information storage in the hippocampal network.

Efficient microwave frequency conversion mediated by a photonics compatible silicon nitride nanobeam oscillator - Fink, Johannes M; Kalaee, M.; Norte, R.; Pitanti, A.; Painter, O. (Quantum Science and Technology)
Microelectromechanical systems and integrated photonics provide the basis for many reliable and compact circuit elements in modern communication systems. Electro-opto-mechanical devices are currently one of the leading approaches to realize ultra-sensitive, low-loss transducers for an emerging quantum information technology. Here we present an on-chip microwave frequency converter based on a planar aluminum on silicon nitride platform that is compatible with slot-mode coupled photonic crystal cavities. We show efficient frequency conversion between two propagating microwave modes mediated by the radiation pressure interaction with a metalized dielectric nanobeam oscillator. We achieve bidirectional coherent conversion with a total device efficiency of up to ~60%, a dynamic range of 2 × 10^9 photons/s and an instantaneous bandwidth of up to 1.7 kHz. A high fidelity quantum state transfer would be possible if the drive dependent output noise of currently ~14 photons s^−1 Hz^−1 is further reduced. Such a silicon nitride based transducer is in situ reconfigurable and could be used for on-chip classical and quantum signal routing and filtering, both for microwave and hybrid microwave-optical applications.

Charge transfer and chemo-mechanical coupling in respiratory complex I - Gupta, Chitrak; Khaniya, Umesh; Chan, Chun Kit; Dehez, Francois; Shekhar, Mrinal; Gunner, M. R.; Sazanov, Leonid A; Chipot, Christophe; Singharoy, Abhishek (Journal of the American Chemical Society)
The mitochondrial respiratory chain, formed by five protein complexes, utilizes energy from catabolic processes to synthesize ATP. Complex I, the first and the largest protein complex of the chain, harvests electrons from NADH to reduce quinone, while pumping protons across the mitochondrial membrane. Detailed knowledge of the working principle of such coupled charge-transfer processes remains, however, fragmentary due to bottlenecks in understanding redox-driven conformational transitions and their interplay with the hydrated proton pathways. Complex I from Thermus thermophilus encases 16 subunits with nine iron–sulfur clusters, reduced by electrons from NADH. Here, employing the latest crystal structure of T. thermophilus complex I, we have used microsecond-scale molecular dynamics simulations to study the chemo-mechanical coupling between redox changes of the iron–sulfur clusters and conformational transitions across complex I. First, we identify the redox switches within complex I, which allosterically couple the dynamics of the quinone binding pocket to the site of NADH reduction. Second, our free-energy calculations reveal that the affinity of the quinone, specifically menaquinone, for the binding-site is higher than that of its reduced, menaquinol form—a design essential for menaquinol release. Remarkably, the barriers to diffusive menaquinone dynamics are lesser than that of the more ubiquitous ubiquinone, and the naphthoquinone headgroup of the former furnishes stronger binding interactions with the pocket, favoring menaquinone for charge transport in T. thermophilus. Our computations are consistent with experimentally validated mutations and hierarchize the key residues into three functional classes, identifying new mutation targets. Third, long-range hydrogen-bond networks connecting the quinone-binding site to the transmembrane subunits are found to be responsible for proton pumping. Put together, the simulations reveal the molecular design principles linking redox reactions to quinone turnover to proton translocation in complex I.

Magnetically powered metachronal waves induce locomotion in self-assemblies - Collard, Ylona; Grosjean, Galien M; Vandewalle, Nicolas (Communications Physics)
When tiny soft ferromagnetic particles are placed along a liquid interface and exposed to a vertical magnetic field, the balance between capillary attraction and magnetic repulsion leads to self-organization into well-defined patterns. Here, we demonstrate experimentally that precessing magnetic fields induce metachronal waves on the periphery of these assemblies, similar to the ones observed in ciliates and some arthropods. The outermost layer of particles behaves like an array of cilia or legs whose sequential movement causes a net and controllable locomotion. This bioinspired many-particle swimming strategy is effective even at low Reynolds number, using only spatially uniform fields to generate the waves.

Oblique stripe solutions of channel flow - Paranjape, Chaitanya S; Duguet, Yohann; Hof, Björn (Journal of Fluid Mechanics)
With decreasing Reynolds number, Re, turbulence in channel flow becomes spatio-temporally intermittent and self-organises into solitary stripes oblique to the mean flow direction. We report here the existence of localised nonlinear travelling wave solutions of the Navier–Stokes equations possessing this obliqueness property. Such solutions are identified numerically using edge tracking coupled with arclength continuation. All solutions emerge in saddle-node bifurcations at values of Re lower than the non-localised solutions. Relative periodic orbit solutions bifurcating from branches of travelling waves have also been computed. A complete parametric study is performed, including their stability, the investigation of their large-scale flow, and the robustness to changes of the numerical domain.

Charge transfer and chemo-mechanical coupling in respiratory complex I - Gupta, Chitrak; Khaniya, Umesh; Chan, Chun; Dehez, Francois; Shekhar, Mrinal; Gunner, M. R.; Sazanov, Leonid A; Chipot, Christophe; Singharoy, Abhishek
The mitochondrial respiratory chain, formed by five protein complexes, utilizes energy from catabolic processes to synthesize ATP. Complex I, the first and the largest protein complex of the chain, harvests electrons from NADH to reduce quinone, while pumping protons across the mitochondrial membrane. Detailed knowledge of the working principle of such coupled charge-transfer processes remains, however, fragmentary due to bottlenecks in understanding redox-driven conformational transitions and their interplay with the hydrated proton pathways. Complex I from Thermus thermophilus encases 16 subunits with nine iron–sulfur clusters, reduced by electrons from NADH. Here, employing the latest crystal structure of T. thermophilus complex I, we have used microsecond-scale molecular dynamics simulations to study the chemo-mechanical coupling between redox changes of the iron–sulfur clusters and conformational transitions across complex I. First, we identify the redox switches within complex I, which allosterically couple the dynamics of the quinone binding pocket to the site of NADH reduction. Second, our free-energy calculations reveal that the affinity of the quinone, specifically menaquinone, for the binding-site is higher than that of its reduced, menaquinol forma design essential for menaquinol release. Remarkably, the barriers to diffusive menaquinone dynamics are lesser than that of the more ubiquitous ubiquinone, and the naphthoquinone headgroup of the former furnishes stronger binding interactions with the pocket, favoring menaquinone for charge transport in T. thermophilus. Our computations are consistent with experimentally validated mutations and hierarchize the key residues into three functional classes, identifying new mutation targets. Third, long-range hydrogen-bond networks connecting the quinone-binding site to the transmembrane subunits are found to be responsible for proton pumping. Put together, the simulations reveal the molecular design principles linking redox reactions to quinone turnover to proton translocation in complex I.

The excitation spectrum of Bose gases interacting through singular potentials - Boccato, Chiara; Brennecke, Christian; Cenatiempo, Serena; Schlein, Benjamin (Journal of the European Mathematical Society)
We consider systems of N bosons in a box of volume one, interacting through a repulsive two-body potential of the form κN3β−1V(Nβx). For all 0<β<1, and for sufficiently small coupling constant κ>0, we establish the validity of Bogolyubov theory, identifying the ground state energy and the low-lying excitation spectrum up to errors that vanish in the limit of large N.

Supporting information - Gupta, Chitrak; Khaniya, Umesh; Chan, Chun Kit; Dehez, Francois; Shekhar, Mrinal; Gunner, M.R.; Sazanov, Leonid A; Chipot, Christophe; Singharoy, Abhishek
Additional analyses of the trajectories

Movies - Gupta, Chitrak; Khaniya, Umesh; Chan, Chun Kit; Dehez, Francois; Shekhar, Mrinal; Gunner, M.R.; Sazanov, Leonid A; Chipot, Christophe; Singharoy, Abhishek

EGFR/Ras-induced CCL20 production modulates the tumour microenvironment - Hippe, Andreas; Braun, Stephan Alexander; Oláh, Péter; Gerber, Peter Arne; Schorr, Anne; Seeliger, Stephan; Holtz, Stephanie; Jannasch, Katharina; Pivarcsi, Andor; Buhren, Bettina; Schrumpf, Holger; Kislat, Andreas; et al. (British Journal of Cancer)
Background: The activation of the EGFR/Ras-signalling pathway in tumour cells induces a distinct chemokine repertoire, which in turn modulates the tumour microenvironment. Methods: The effects of EGFR/Ras on the expression and translation of CCL20 were analysed in a large set of epithelial cancer cell lines and tumour tissues by RT-qPCR and ELISA in vitro. CCL20 production was verified by immunohistochemistry in different tumour tissues and correlated with clinical data. The effects of CCL20 on endothelial cell migration and tumour-associated vascularisation were comprehensively analysed with chemotaxis assays in vitro and in CCR6-deficient mice in vivo. Results: Tumours facilitate progression by the EGFR/Ras-induced production of CCL20. Expression of the chemokine CCL20 in tumours correlates with advanced tumour stage, increased lymph node metastasis and decreased survival in patients. Microvascular endothelial cells abundantly express the specific CCL20 receptor CCR6. CCR6 signalling in endothelial cells induces angiogenesis. CCR6-deficient mice show significantly decreased tumour growth and tumour-associated vascularisation. The observed phenotype is dependent on CCR6 deficiency in stromal cells but not within the immune system. Conclusion: We propose that the chemokine axis CCL20–CCR6 represents a novel and promising target to interfere with the tumour microenvironment, and opens an innovative multimodal strategy for cancer therapy.

Emergence of Haldane pseudo-potentials in systems with short-range interactions - Seiringer, Robert; Yngvason, Jakob (Journal of Statistical Physics)
In the setting of the fractional quantum Hall effect we study the effects of strong, repulsive two-body interaction potentials of short range. We prove that Haldane’s pseudo-potential operators, including their pre-factors, emerge as mathematically rigorous limits of such interactions when the range of the potential tends to zero while its strength tends to infinity. In a common approach the interaction potential is expanded in angular momentum eigenstates in the lowest Landau level, which amounts to taking the pre-factors to be the moments of the potential. Such a procedure is not appropriate for very strong interactions, however, in particular not in the case of hard spheres. We derive the formulas valid in the short-range case, which involve the scattering lengths of the interaction potential in different angular momentum channels rather than its moments. Our results hold for bosons and fermions alike and generalize previous results in [6], which apply to bosons in the lowest angular momentum channel. Our main theorem asserts the convergence in a norm-resolvent sense of the Hamiltonian on the whole Hilbert space, after appropriate energy scalings, to Hamiltonians with contact interactions in the lowest Landau level.

Projection methods with alternating inertial steps for variational inequalities: Weak and linear convergence - Shehu, Yekini; Iyiola, Olaniyi S. (Applied Numerical Mathematics)
The projection methods with vanilla inertial extrapolation step for variational inequalities have been of interest to many authors recently due to the improved convergence speed contributed by the presence of inertial extrapolation step. However, it is discovered that these projection methods with inertial steps lose the Fejér monotonicity of the iterates with respect to the solution, which is being enjoyed by their corresponding non-inertial projection methods for variational inequalities. This lack of Fejér monotonicity makes projection methods with vanilla inertial extrapolation step for variational inequalities not to converge faster than their corresponding non-inertial projection methods at times. Also, it has recently been proved that the projection methods with vanilla inertial extrapolation step may provide convergence rates that are worse than the classical projected gradient methods for strongly convex functions. In this paper, we introduce projection methods with alternated inertial extrapolation step for solving variational inequalities. We show that the sequence of iterates generated by our methods converges weakly to a solution of the variational inequality under some appropriate conditions. The Fejér monotonicity of even subsequence is recovered in these methods and linear rate of convergence is obtained. The numerical implementations of our methods compared with some other inertial projection methods show that our method is more efficient and outperforms some of these inertial projection methods.

Tin selenide molecular precursor for the solution processing of thermoelectric materials and devices - Zhang, Yu; Liu, Yu; Xing, Congcong; Zhang, Ting; Li, Mengyao; Pacios, Mercè; Yu, Xiaoting; Arbiol, Jordi; Llorca, Jordi; Cadavid, Doris; Ibáñez, Maria; Cabot, Andreu (ACS Applied Materials and Interfaces)
In the present work, we report a solution-based strategy to produce crystallographically textured SnSe bulk nanomaterials and printed layers with optimized thermoelectric performance in the direction normal to the substrate. Our strategy is based on the formulation of a molecular precursor that can be continuously decomposed to produce a SnSe powder or printed into predefined patterns. The precursor formulation and decomposition conditions are optimized to produce pure phase 2D SnSe nanoplates. The printed layer and the bulk material obtained after hot press displays a clear preferential orientation of the crystallographic domains, resulting in an ultralow thermal conductivity of 0.55 W m–1 K–1 in the direction normal to the substrate. Such textured nanomaterials present highly anisotropic properties with the best thermoelectric performance in plane, i.e., in the directions parallel to the substrate, which coincide with the crystallographic bc plane of SnSe. This is an unfortunate characteristic because thermoelectric devices are designed to create/harvest temperature gradients in the direction normal to the substrate. We further demonstrate that this limitation can be overcome with the introduction of small amounts of tellurium in the precursor. The presence of tellurium allows one to reduce the band gap and increase both the charge carrier concentration and the mobility, especially the cross plane, with a minimal decrease of the Seebeck coefficient. These effects translate into record out of plane ZT values at 800 K.

Multi-method genome- and epigenome-wide studies of inflammatory protein levels in healthy older adults - Hillary, Robert F.; Trejo-Banos, Daniel; Kousathanas, Athanasios; Mccartney, Daniel L.; Harris, Sarah E.; Stevenson, Anna J.; Patxot, Marion; Ojavee, Sven Erik; Zhang, Qian; Liewald, David C.; Ritchie, Craig W.; Evans, Kathryn L.; et al. (Genome Medicine)
The molecular factors which control circulating levels of inflammatory proteins are not well understood. Furthermore, association studies between molecular probes and human traits are often performed by linear model-based methods which may fail to account for complex structure and interrelationships within molecular datasets.In this study, we perform genome- and epigenome-wide association studies (GWAS/EWAS) on the levels of 70 plasma-derived inflammatory protein biomarkers in healthy older adults (Lothian Birth Cohort 1936; n = 876; Olink® inflammation panel). We employ a Bayesian framework (BayesR+) which can account for issues pertaining to data structure and unknown confounding variables (with sensitivity analyses using ordinary least squares- (OLS) and mixed model-based approaches). We identified 13 SNPs associated with 13 proteins (n = 1 SNP each) concordant across OLS and Bayesian methods. We identified 3 CpG sites spread across 3 proteins (n = 1 CpG each) that were concordant across OLS, mixed-model and Bayesian analyses. Tagged genetic variants accounted for up to 45% of variance in protein levels (for MCP2, 36% of variance alone attributable to 1 polymorphism). Methylation data accounted for up to 46% of variation in protein levels (for CXCL10). Up to 66% of variation in protein levels (for VEGFA) was explained using genetic and epigenetic data combined. We demonstrated putative causal relationships between CD6 and IL18R1 with inflammatory bowel disease and between IL12B and Crohn’s disease. Our data may aid understanding of the molecular regulation of the circulating inflammatory proteome as well as causal relationships between inflammatory mediators and disease.

Training deep neural density estimators to identify mechanistic models of neural dynamics - Gonçalves, Pedro J.; Lueckmann, Jan-Matthis; Deistler, Michael; Nonnenmacher, Marcel; Öcal, Kaan; Bassetto, Giacomo; Chintaluri, Chaitanya; Podlaski, William F.; Haddad, Sara A.; Vogels, Tim P; Greenberg, David S.; Macke, Jakob H. (eLife)
Mechanistic modeling in neuroscience aims to explain observed phenomena in terms of underlying causes. However, determining which model parameters agree with complex and stochastic neural data presents a significant challenge. We address this challenge with a machine learning tool which uses deep neural density estimators—trained using model simulations—to carry out Bayesian inference and retrieve the full space of parameters compatible with raw data or selected data features. Our method is scalable in parameters and data features and can rapidly analyze new data after initial training. We demonstrate the power and flexibility of our approach on receptive fields, ion channels, and Hodgkin–Huxley models. We also characterize the space of circuit configurations giving rise to rhythmic activity in the crustacean stomatogastric ganglion, and use these results to derive hypotheses for underlying compensation mechanisms. Our approach will help close the gap between data-driven and theory-driven models of neural dynamics.

Complementary inhibitory weight profiles emerge from plasticity and allow attentional switching of receptive fields - Agnes, Everton J.; Luppi, Andrea I.; Vogels, Tim P (The Journal of Neuroscience)
Cortical areas comprise multiple types of inhibitory interneurons with stereotypical connectivity motifs, but their combined effect on postsynaptic dynamics has been largely unexplored. Here, we analyse the response of a single postsynaptic model neuron receiving tuned excitatory connections alongside inhibition from two plastic populations. Depending on the inhibitory plasticity rule, synapses remain unspecific (flat), become anti-correlated to, or mirror excitatory synapses. Crucially, the neuron’s receptive field, i.e., its response to presynaptic stimuli, depends on the modulatory state of inhibition. When both inhibitory populations are active, inhibition balances excitation, resulting in uncorrelated postsynaptic responses regardless of the inhibitory tuning profiles. Modulating the activity of a given inhibitory population produces strong correlations to either preferred or non-preferred inputs, in line with recent experimental findings showing dramatic context-dependent changes of neurons’ receptive fields. We thus confirm that a neuron’s receptive field doesn’t follow directly from the weight profiles of its presynaptic afferents.

The cytoskeletal regulator HEM1 governs B cell development and prevents autoimmunity - Salzer, Elisabeth; Zoghi, Samaneh; Kiss, Máté G.; Kage, Frieda; Rashkova, Christina; Stahnke, Stephanie; Haimel, Matthias; Platzer, René; Caldera, Michael; Ardy, Rico Chandra; Hoeger, Birgit; Block, Jana; et al. (Science Immunology)
The WAVE regulatory complex (WRC) is crucial for assembly of the peripheral branched actin network constituting one of the main drivers of eukaryotic cell migration. Here, we uncover an essential role of the hematopoietic-specific WRC component HEM1 for immune cell development. Germline-encoded HEM1 deficiency underlies an inborn error of immunity with systemic autoimmunity, at cellular level marked by WRC destabilization, reduced filamentous actin, and failure to assemble lamellipodia. Hem1−/− mice display systemic autoimmunity, phenocopying the human disease. In the absence of Hem1, B cells become deprived of extracellular stimuli necessary to maintain the strength of B cell receptor signaling at a level permissive for survival of non-autoreactive B cells. This shifts the balance of B cell fate choices toward autoreactive B cells and thus autoimmunity.

Additional file 2 of multi-method genome- and epigenome-wide studies of inflammatory protein levels in healthy older adults - Hillary, Robert F.; Trejo-Banos, Daniel; Kousathanas, Athanasios; McCartney, Daniel L.; Harris, Sarah E.; Stevenson, Anna J.; Patxot, Marion; Ojavee, Sven Erik; Zhang, Qian; Liewald, David C.; Ritchie, Craig W.; Evans, Kathryn L.; et al.
Additional file 2: Supplementary Tables. The association of pre-adjusted protein levels with biological and technical covariates. Protein levels were adjusted for age, sex, array plate and four genetic principal components (population structure) prior to analyses. Significant associations are emboldened. (Table S1). pQTLs associated with inflammatory biomarker levels from Bayesian penalised regression model (Posterior Inclusion Probability > 95%). (Table S2). All pQTLs associated with inflammatory biomarker levels from ordinary least squares regression model (P < 7.14 × 10− 10). (Table S3). Summary of lambda values relating to ordinary least squares GWAS and EWAS performed on inflammatory protein levels (n = 70) in Lothian Birth Cohort 1936 study. (Table S4). Conditionally significant pQTLs associated with inflammatory biomarker levels from ordinary least squares regression model (P < 7.14 × 10− 10). (Table S5). Comparison of variance explained by ordinary least squares and Bayesian penalised regression models for concordantly identified SNPs. (Table S6). Estimate of heritability for blood protein levels as well as proportion of variance explained attributable to different prior mixtures. (Table S7). Comparison of heritability estimates from Ahsan et al. (maximum likelihood) and Hillary et al. (Bayesian penalised regression). (Table S8). List of concordant SNPs identified by linear model and Bayesian penalised regression and whether they have been previously identified as eQTLs. (Table S9). Bayesian tests of colocalisation for cis pQTLs and cis eQTLs. (Table S10). Sherlock algorithm: Genes whose expression are putatively associated with circulating inflammatory proteins that harbour pQTLs. (Table S11). CpGs associated with inflammatory protein biomarkers as identified by Bayesian model (Bayesian model; Posterior Inclusion Probability > 95%). (Table S12). CpGs associated with inflammatory protein biomarkers as identified by linear model (limma) at P < 5.14 × 10− 10. (Table S13). CpGs associated with inflammatory protein biomarkers as identified by mixed linear model (OSCA) at P < 5.14 × 10− 10. (Table S14). Estimate of variance explained for blood protein levels by DNA methylation as well as proportion of explained attributable to different prior mixtures - BayesR+. (Table S15). Comparison of variance in protein levels explained by genome-wide DNA methylation data by mixed linear model (OSCA) and Bayesian penalised regression model (BayesR+). (Table S16). Variance in circulating inflammatory protein biomarker levels explained by common genetic and methylation data (joint and conditional estimates from BayesR+). Ordered by combined variance explained by genetic and epigenetic data - smallest to largest. Significant results from t-tests comparing distributions for variance explained by methylation or genetics alone versus combined estimate are emboldened. (Table S17). Genetic and epigenetic factors identified by BayesR+ when conditioning on all SNPs and CpGs together. (Table S18). Mendelian Randomisation analyses to assess whether proteins with concordantly identified genetic signals are causally associated with Alzheimer’s disease risk. (Table S19).

The free energy of the two-dimensional dilute Bose gas. II. Upper bound - Mayer, Simon; Seiringer, Robert (Journal of Mathematical Physics)
We prove an upper bound on the free energy of a two-dimensional homogeneous Bose gas in the thermodynamic limit. We show that for a2ρ ≪ 1 and βρ ≳ 1, the free energy per unit volume differs from the one of the non-interacting system by at most 4πρ2|lna2ρ|−1(2−[1−βc/β]2+) to leading order, where a is the scattering length of the two-body interaction potential, ρ is the density, β is the inverse temperature, and βc is the inverse Berezinskii–Kosterlitz–Thouless critical temperature for superfluidity. In combination with the corresponding matching lower bound proved by Deuchert et al. [Forum Math. Sigma 8, e20 (2020)], this shows equality in the asymptotic expansion.

On the completion of speciation - Barton, Nicholas H (Philosophical Transactions of the Royal Society. Series B: Biological Sciences)

Cell-type specificity of genomic imprinting in cerebral cortex - Laukoter, Susanne; Pauler, Florian; Beattie, Robert J; Amberg, Nicole; Hansen, Andi H; Streicher, Carmen; Penz, Thomas; Bock, Christoph; Hippenmeyer, Simon (Neuron)
In mammalian genomes, a subset of genes is regulated by genomic imprinting, resulting in silencing of one parental allele. Imprinting is essential for cerebral cortex development, but prevalence and functional impact in individual cells is unclear. Here, we determined allelic expression in cortical cell types and established a quantitative platform to interrogate imprinting in single cells. We created cells with uniparental chromosome disomy (UPD) containing two copies of either the maternal or the paternal chromosome; hence, imprinted genes will be 2-fold overexpressed or not expressed. By genetic labeling of UPD, we determined cellular phenotypes and transcriptional responses to deregulated imprinted gene expression at unprecedented single-cell resolution. We discovered an unexpected degree of cell-type specificity and a novel function of imprinting in the regulation of cortical astrocyte survival. More generally, our results suggest functional relevance of imprinted gene expression in glial astrocyte lineage and thus for generating cortical cell-type diversity.

Strigolactones inhibit auxin feedback on PIN-dependent auxin transport canalization - Zhang, J; Mazur, E; Balla, J; Gallei, Michelle C; Kalousek, P; Medveďová, Z; Li, Y; Wang, Y; Prat, Tomas; Vasileva, Mina K; Reinöhl, V; Procházka, S; et al. (Nature Communications)
Directional transport of the phytohormone auxin is a versatile, plant-specific mechanism regulating many aspects of plant development. The recently identified plant hormones, strigolactones (SLs), are implicated in many plant traits; among others, they modify the phenotypic output of PIN-FORMED (PIN) auxin transporters for fine-tuning of growth and developmental responses. Here, we show in pea and Arabidopsis that SLs target processes dependent on the canalization of auxin flow, which involves auxin feedback on PIN subcellular distribution. D14 receptor- and MAX2 F-box-mediated SL signaling inhibits the formation of auxin-conducting channels after wounding or from artificial auxin sources, during vasculature de novo formation and regeneration. At the cellular level, SLs interfere with auxin effects on PIN polar targeting, constitutive PIN trafficking as well as clathrin-mediated endocytosis. Our results identify a non-transcriptional mechanism of SL action, uncoupling auxin feedback on PIN polarity and trafficking, thereby regulating vascular tissue formation and regeneration.

Towards the completion of speciation: The evolution of reproductive isolation beyond the first barriers - Kulmuni, Jonna; Butlin, Roger K.; Lucek, Kay; Savolainen, Vincent; Westram, Anja M (Philosophical Transactions of the Royal Society. Series B: Biological sciences)
Speciation, that is, the evolution of reproductive barriers eventually leading to complete isolation, is a crucial process generating biodiversity. Recent work has contributed much to our understanding of how reproductive barriers begin to evolve, and how they are maintained in the face of gene flow. However, little is known about the transition from partial to strong reproductive isolation (RI) and the completion of speciation. We argue that the evolution of strong RI is likely to involve different processes, or new interactions among processes, compared with the evolution of the first reproductive barriers. Transition to strong RI may be brought about by changing external conditions, for example, following secondary contact. However, the increasing levels of RI themselves create opportunities for new barriers to evolve and, and interaction or coupling among barriers. These changing processes may depend on genomic architecture and leave detectable signals in the genome. We outline outstanding questions and suggest more theoretical and empirical work, considering both patterns and processes associated with strong RI, is needed to understand how speciation is completed.

The evolution of strong reproductive isolation between sympatric intertidal snails - Stankowski, Sean; Westram, Anja M; Zagrodzka, Zuzanna B.; Eyres, Isobel; Broquet, Thomas; Johannesson, Kerstin; Butlin, Roger K. (Philosophical Transactions of the Royal Society. Series B: Biological Sciences)
The evolution of strong reproductive isolation (RI) is fundamental to the origins and maintenance of biological diversity, especially in situations where geographical distributions of taxa broadly overlap. But what is the history behind strong barriers currently acting in sympatry? Using whole-genome sequencing and single nucleotide polymorphism genotyping, we inferred (i) the evolutionary relationships, (ii) the strength of RI, and (iii) the demographic history of divergence between two broadly sympatric taxa of intertidal snail. Despite being cryptic, based on external morphology, Littorina arcana and Littorina saxatilis differ in their mode of female reproduction (egg-laying versus brooding), which may generate a strong post-zygotic barrier. We show that egg-laying and brooding snails are closely related, but genetically distinct. Genotyping of 3092 snails from three locations failed to recover any recent hybrid or backcrossed individuals, confirming that RI is strong. There was, however, evidence for a very low level of asymmetrical introgression, suggesting that isolation remains incomplete. The presence of strong, asymmetrical RI was further supported by demographic analysis of these populations. Although the taxa are currently broadly sympatric, demographic modelling suggests that they initially diverged during a short period of geographical separation involving very low gene flow. Our study suggests that some geographical separation may kick-start the evolution of strong RI, facilitating subsequent coexistence of taxa in sympatry. The strength of RI needed to achieve sympatry and the subsequent effect of sympatry on RI remain open questions.

Rotational coherence spectroscopy of molecules in Helium nanodroplets: Reconciling the time and the frequency domains - Chatterley, Adam S.; Christiansen, Lars; Schouder, Constant A.; Jørgensen, Anders V.; Shepperson, Benjamin; Cherepanov, Igor; Bighin, Giacomo; Zillich, Robert E.; Lemeshko, Mikhail; Stapelfeldt, Henrik (Physical Review Letters)
Alignment of OCS, CS2, and I2 molecules embedded in helium nanodroplets is measured as a function of time following rotational excitation by a nonresonant, comparatively weak ps laser pulse. The distinct peaks in the power spectra, obtained by Fourier analysis, are used to determine the rotational, B, and centrifugal distortion, D, constants. For OCS, B and D match the values known from IR spectroscopy. For CS2 and I2, they are the first experimental results reported. The alignment dynamics calculated from the gas-phase rotational Schrödinger equation, using the experimental in-droplet B and D values, agree in detail with the measurement for all three molecules. The rotational spectroscopy technique for molecules in helium droplets introduced here should apply to a range of molecules and complexes.

An SMT theory of fixed-point arithmetic - Baranowski, Marek; He, Shaobo; Lechner, Mathias; Nguyen, Thanh Son; Rakamarić, Zvonimir (Automated Reasoning)
Fixed-point arithmetic is a popular alternative to floating-point arithmetic on embedded systems. Existing work on the verification of fixed-point programs relies on custom formalizations of fixed-point arithmetic, which makes it hard to compare the described techniques or reuse the implementations. In this paper, we address this issue by proposing and formalizing an SMT theory of fixed-point arithmetic. We present an intuitive yet comprehensive syntax of the fixed-point theory, and provide formal semantics for it based on rational arithmetic. We also describe two decision procedures for this theory: one based on the theory of bit-vectors and the other on the theory of reals. We implement the two decision procedures, and evaluate our implementations using existing mature SMT solvers on a benchmark suite we created. Finally, we perform a case study of using the theory we propose to verify properties of quantized neural networks.

Evolution of strong reproductive isolation in plants: Broad-scale patterns and lessons from a perennial model group - Shang, Huiying; Hess, Jaqueline; Pickup, Melinda; Field, David; Ingvarsson, Pär K.; Liu, Jianquan; Lexer, Christian (Philosophical Transactions of the Royal Society. Series B: Biological Sciences)
Many recent studies have addressed the mechanisms operating during the early stages of speciation, but surprisingly few studies have tested theoretical predictions on the evolution of strong reproductive isolation (RI). To help address this gap, we first undertook a quantitative review of the hybrid zone literature for flowering plants in relation to reproductive barriers. Then, using Populus as an exemplary model group, we analysed genome-wide variation for phylogenetic tree topologies in both early- and late-stage speciation taxa to determine how these patterns may be related to the genomic architecture of RI. Our plant literature survey revealed variation in barrier complexity and an association between barrier number and introgressive gene flow. Focusing on Populus, our genome-wide analysis of tree topologies in speciating poplar taxa points to unusually complex genomic architectures of RI, consistent with earlier genome-wide association studies. These architectures appear to facilitate the ‘escape’ of introgressed genome segments from polygenic barriers even with strong RI, thus affecting their relationships with recombination rates. Placed within the context of the broader literature, our data illustrate how phylogenomic approaches hold great promise for addressing the evolution and temporary breakdown of RI during late stages of speciation.

Phosphorous incorporation in Pd2Sn alloys for electrocatalytic ethanol oxidation - Yu, Xiaoting; Liu, Junfeng; Li, Junshan; Luo, Zhishan; Zuo, Yong; Xing, Congcong; Llorca, Jordi; Nasiou, Déspina; Arbiol, Jordi; Pan, Kai; Kleinhanns, Tobias; Xie, Ying; et al. (Nano Energy)
Direct ethanol fuel cells (DEFCs) show a huge potential to power future electric vehicles and portable electronics, but their deployment is currently limited by the unavailability of proper electrocatalysis for the ethanol oxidation reaction (EOR). In this work, we engineer a new electrocatalyst by incorporating phosphorous into a palladium-tin alloy and demonstrate a significant performance improvement toward EOR. We first detail a synthetic method to produce Pd2Sn:P nanocrystals that incorporate 35% of phosphorus. These nanoparticles are supported on carbon black and tested for EOR. Pd2Sn:P/C catalysts exhibit mass current densities up to 5.03 A mgPd−1, well above those of Pd2Sn/C, PdP2/C and Pd/C reference catalysts. Furthermore, a twofold lower Tafel slope and a much longer durability are revealed for the Pd2Sn:P/C catalyst compared with Pd/C. The performance improvement is rationalized with the aid of density functional theory (DFT) calculations considering different phosphorous chemical environments. Depending on its oxidation state, surface phosphorus introduces sites with low energy OH− adsorption and/or strongly influences the electronic structure of palladium and tin to facilitate the oxidation of the acetyl to acetic acid, which is considered the EOR rate limiting step. DFT calculations also points out that the durability improvement of Pd2Sn:P/C catalyst is associated to the promotion of OH adsorption that accelerates the oxidation of intermediate poisoning COads, reactivating the catalyst surface.

Stem cell lineage survival as a noisy competition for niche access - Corominas-Murtra, Bernat; Scheele, Colinda L.G.J.; Kishi, Kasumi; Ellenbroek, Saskia I.J.; Simons, Benjamin D.; Van Rheenen, Jacco; Hannezo, Edouard B (Proceedings of the National Academy of Sciences of the United States of America)
Understanding to what extent stem cell potential is a cell-intrinsic property or an emergent behavior coming from global tissue dynamics and geometry is a key outstanding question of systems and stem cell biology. Here, we propose a theory of stem cell dynamics as a stochastic competition for access to a spatially localized niche, giving rise to a stochastic conveyor-belt model. Cell divisions produce a steady cellular stream which advects cells away from the niche, while random rearrangements enable cells away from the niche to be favorably repositioned. Importantly, even when assuming that all cells in a tissue are molecularly equivalent, we predict a common (“universal”) functional dependence of the long-term clonal survival probability on distance from the niche, as well as the emergence of a well-defined number of functional stem cells, dependent only on the rate of random movements vs. mitosis-driven advection. We test the predictions of this theory on datasets of pubertal mammary gland tips and embryonic kidney tips, as well as homeostatic intestinal crypts. Importantly, we find good agreement for the predicted functional dependency of the competition as a function of position, and thus functional stem cell number in each organ. This argues for a key role of positional fluctuations in dictating stem cell number and dynamics, and we discuss the applicability of this theory to other settings.

Exponentially long lifetime of universal quasi-steady states in topological Floquet pumps - Gulden, Tobias; Berg, Erez; Rudner, Mark Spencer; Lindner, Netanel (SciPost Physics)
We investigate a mechanism to transiently stabilize topological phenomena in long-lived quasi-steady states of isolated quantum many-body systems driven at low frequencies. We obtain an analytical bound for the lifetime of the quasi-steady states which is exponentially large in the inverse driving frequency. Within this lifetime, the quasi-steady state is characterized by maximum entropy subject to the constraint of fixed number of particles in the system's Floquet-Bloch bands. In such a state, all the non-universal properties of these bands are washed out, hence only the topological properties persist.